Mechanistic insights into low-dose nZVI-enhanced process stability under variable industrial loads in field-scale anaerobic treatment: Interfacial evolution and strain-resolved adaptation - Zhihong Gao; Lijing Xue; Yujia Ma; Chen Chen; Hong Ling; Lin Wang; Weiming Zhang; Jieshu Qian; Zhichao Yang; Ming Hua; Bingcai Pan (Water Research, 2026)

TBBPA facilitates splenic inflammation and pyroptosis by targeting HMGB1 - Fu-Wei Jiang; Jing-Han Lin; Jia-Xin Wang; Ming-Shan Chen; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Ming Lou; Zi-Yan Hu; Yi Zhao; Jin-Long Li (Journal of Environmental Sciences, 2026)

Sex peptide receptor modulates sex pheromone perception plasticity in female Galleria mellonella across mating status - Zhen-Ping Guo; Xu-Dong Pang; Li-Lin Luo; Ming-Qing Yu; Jun-Hong Linghu; Hua-Yan Xie; Guy Smagghe; Tong-Xian Liu; Shun-Hua Gui (Insect Biochemistry and Molecular Biology, 2026)

Caged xanthones with cytotoxic activity from the leaves and twigs of Garcinia oligantha - Xiao-Hui Peng; Sha Chen; Si-Yu Wang; Jin-Yuan Yang; Hao-Nan Li; Bin Lin; Hui-Ming Hua; Da-Hong Li (Phytochemistry, 2026)

Unraveling the anti-listerial activity of noni fruit essential oil: Omics-based mechanistic insights and application in salmon preservation - Qiongping Hong; Jiamu Kang; Xinyu Li; Shanshan Zheng; Ming Yang; Lin Zhang; Yuyun Lu (International Journal of Food Microbiology, 2026)

Beyond mortality: A multi-outcome assessment of health economic benefits from air pollution control in China - Hao-Wen Liao; Zhi-Ming Han; Guo-Ping Dong; Duo-Hong Chen; Min Xie; Jun Liu; Junyu Zheng; Yun-Ting Zhang; Haseeb Tufail Moryani; Muhammad Amjad; Yang Zhou; Wen-Wen Bao; et al. (Environmental Research, 2026)

Corrigendum to “Associations between multiple metals exposure and cognitive function in the middle-aged and older adults from China: A cross-sectional study” [Environ. Res., 263(Pt 1), 2024, 120038] - Shiru Hong; Sheng Wu; Zhengce Wan; Chenming Wang; Xin Guan; Ming Fu; Chenliang Liu; Tianhao Wu; Guorong Zhong; Yuhan Zhou; Yang Xiao; Yingqian You; et al. (Environmental Research, 2026)

Piezoresistive AgNPs-MXene/TPU strain sensors with hierarchical microstructures via template-assisted phase separation and in-situ growth for health monitoring and emergency rescue - Guanting Wu; Songyue Pan; Chuanxi Lin; Weijie Wang; Jiatong Yan; Ming Zhong; Hong Tang; Ronghui Guo (Chemical Engineering Journal, 2026)

Lithium-doped calcium silicate scaffolds induce miR-130a-rich M2 macrophage EV-accelerating diabetic bone healing through angiogenesis–osteogenic coupling and mitochondrial repair - Ting-You Kuo; Cheng-Yu Chen; Yen-Hong Lin; Der-Yang Cho; Tsung-Li Lin; Ming-You Shie (Chemical Engineering Journal, 2026)

Identify conservation gaps and devise sustainable use strategies using orchid flora as a proxy - Hong Liu; Emily Jefferson; Shao-Ting Lin; Che-Yu Lin; Chun-Ming Chen; Dominic Mellone; Wen-Chieh Tsai (Biodiversity and Conservation, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Isolation, structural elucidation, and activities evaluation of proaporphine alkaloids from Thalictrum baicalense - Meng-Yue Yang; Jing-Jing Xue; Zhao-Jing Chen; Xiao-Peng Guo; Shi-Meng Qin; Han-Gao Yang; Fang-Shen Liu; Zhan-Lin Li; Da-Hong Li; Ya-Ting Sun; Hui-Ming Hua (Phytochemistry, 2026)

Permian A-type felsic magmatism in the South Tianshan Orogenic Belt: Crustal melting triggered by the Tarim mantle plume - Zhi-Hao Song; Xian-Tao Ye; Xiao-Qiang Liu; Hong-Ran Wang; Ming-Can Yang; Shun-Hao Fu; Chuan-Lin Zhang (Lithos, 2026)

A novel mitochondrial OMA1-DELE1-HRI axis mediates polystyrene microplastics-induced blood-testis barrier dysfunction - Rong Wang; Zhen Tian; Chen Chen; Ming-Ming Zhang; Ding-Qiang Peng; Ke-Xin Liu; Yu-Tong Ren; Shuai Lin; Qiang Hong; Yan-Li Ji; Yuan-Hua Chen (Journal of Environmental Sciences, 2026)

Short anti-aging peptides from edible microalgae using a multi-targets virtual screening strategy combined with Caenorhabditis elegans model - Yan-yan Yuan; Xin Li; Ming-hui Han; Xue An; Yong-Qiang Lin; Hong-Bing Liu (Food Research International, 2026)

A food-derived octapeptide SRGQIEEL from yellow field pea protein hydrolysates inhibits xanthine oxidase via a tunnel-occlusion-like mechanism - Mei-Ling Li; Cheng-Hong Hsieh; Pei-Yu Wu; Shang-Ming Huang; Chung-Yu Tang; Yu-Shun Lin; Kuo-Chiang Hsu (Food Bioscience, 2026)

Revealing the kinetic promotion mechanism of carbon nanotubes to methane hydrate formation: As to the situation coupled with traditional kinetic promoter L-leucine - Yan Lin; Yan-Ling Guo; Zhi-Yuan Wang; Jie Zhong; Xiao-Ming Wang; Yi-Ning Ding; Hong-Zheng Lu; Fei Wang; Xiao-Lin Wang (Chemical Engineering Journal, 2026)

Circular bioprocessing of bovine blood for peptide-based antimicrobial and antibiofilm agents - Gan Huey; Asif Ali Bhat; Bao-Hong Lee; Ming‐Kuei Shih; Li-Jung Yin; You-Lin Tain; Yu-Wei Chen; Yeu-Ching Shi; Chih-Yao Hou (Bioresource Technology, 2026)

Phage-Display Identification of Urate-Binding Cyclic Peptides with Preliminary Urate-Lowering Activity in Adenine-Induced Hyperuricemic Rats - Mi Ai; Zhi-Ming Wang; Wei-Lin Guo; Xue-Qi Li; Li-Ting Xiao; Yan-Shan Mai; Hong-Bin Zhang (International Journal of Peptide Research and Therapeutics, 2026)

Virulensome: a transient organelle mediating fungal virulence - Pei-Ji Zhao; Qian-Yi Hu; Si-Han Wang; Cheng-Song Wang; Xue-Xian Jian; Xing-Fu Wen; Yu-Lin Luo; Ya-Qi Zhang; Chun-Mei Xiang; Guo-Hong Li; Shu-Qun Liu; Ming-He Mo; et al. (Science China Life Sciences, 2026)

A power-law relationship between bulk modulus and permeability in fractured sandstone: Insights from tidal analysis - Xu-Lin Tang; Xiao-Wei Jiang; Zhe-Ming Shi; Zhi-Yu Qi; De-Qiang Mao; Xu-Sheng Wang; Yan Zhang; Li Wan; Hong-Bin Yan (Engineering Geology, 2026)

Syn-tectonic emplacement of Li-bearing pegmatites related to detachment faulting in the Dahongliutan pegmatite belt, Western Kunlun, NW China - Tao Hong; Matthieu Harlaux; Ming-Guo Zhai; Yue-Jun Wang; Xing-Wang Xu; Xiao-Ping Xia; Jun Gao; Jun-Lin Tang; Ming-Xi Hu; Huan-Xiang Gao (Mineralium Deposita, 2026)

Corrigendum to “Effects of vacuum steam pulsed blanching on bioactive compounds, quality attributes, enzyme activities, and microstructural properties of daylily (Hemerocallis citrina Baroni)” [Food Chem. 506 (2026) 148147] - Jun Zhang; Li-Zheng Deng; Wei-Peng Zhang; Ming-Qiang Xu; You-Sheng Shi; Shi-Han Yu; Jing-Shou Zhang; Fan Yang; Shu-Lin Liu; Wei-Qiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

A mixed-fluid genetic model for the baiceng fluorite deposit, SW China: Deciphering the magmatic thermal driver and basinal fluid sources - Xi-Wen Zhang; Zhong-guo Jin; Ming-hong Zheng; Jun Chen; Ze-liang Yu; Long Luo; Yong-hu Su; Lin Ye; Yan-wen Tang; Min-shan Gun (Earth Science Informatics, 2026)

The combination of Astragalus membranaceus and Lycium barbarum polysaccharides is superior to either alone in enhancing growth and health of grass carp (Ctenopharyngodon idellus) - Wei Zhang; Lin Ma; Yi-Geng Meng; Ke-Ming Liu; Hong-Qing Sun; Chao Cai; Ming-Ze Li; Yuan-Yuan Dai; Wen-Wen Li; Xin Luo; Nan Li (Animal Feed Science and Technology, 2026)

Metabarcoding Chironomid Pupal Exuviae Enables Scalable Biomonitoring With High Comparability to Morphotaxonomy - Wu Han; Chu‐Ming Zhang; Cheng Qian; Tsz‐Ying Chan; Thilina S. Nimalrathna; Bai‐an Lin; Xiao‐Long Lin; Hong‐Qu Tang; Peter S. Cranston; Mathew Seymour (Molecular Ecology, 2026)
Conventional morphotaxonomy‐based biomonitoring requires modernization to enable timely assessments in the face of an accelerating freshwater biodiversity crisis. The Chironomid Pupal Exuviae Technique (CPET) is an established biomonitoring approach with considerable potential for integration with molecular methods, as the shed pupal skins of emerging adults provide a source of DNA. We tested the performance of DNA metabarcoding for detecting species richness, recovering beta‐diversity patterns and assessing biodiversity responses to environmental gradients using 15 mock communities and 12 natural chironomid pupal exuviae samples collected from Hong Kong streams. Additionally, the effects of primer choice were assessed by comparing a chironomid‐specific primer set (COI‐S) against a universal, highly degenerate primer set (COI‐V). Our results show that both primer sets achieved high species detection rates in mock communities (86% and 84%, respectively) and consistently recovered predefined community dissimilarities. In natural community samples, however, only COI‐S produced beta‐diversity patterns significantly congruent with that of the morphological dataset (Procrustes r = 0.74, p = 0.003). Both metabarcoding datasets effectively captured seasonal community shifts and demonstrated greater sensitivity to environmental gradients than traditional morphological identification. Notably, the COI‐S dataset explained the highest proportion of community variation (adjusted R 2 = 44.3%), along the environmental gradient, outperforming both the morphotaxonomy (32.5%) and the COI‐V (29.0%) analyses. Here we propose Meta‐CPET, an integrated framework that combines the ecological relevance of CPET with the efficiency, scalability, and resolution of DNA metabarcoding. Our findings show that bulk‐sample metabarcoding enables practical, standardized and large‐scale freshwater biomonitoring while maintaining strong comparability with conventional methods.

Silkworm excrement–immobilized bacteria for synergistic remediation of phthalate esters in agricultural soil - Yong-Hong Chen; Huan Du; Ying-Xi Liu; Ke Xu; Jin-Cheng Ye; Bai-Lin Liu; Nai-Xian Feng; Lei Xiang; Yan-Wen Li; Quan-Ying Cai; Ce-Hui Mo; Hai-Ming Zhao (Journal of Hazardous Materials, 2026)

Corrigendum to “AI-driven process-tolerant BioFET sensing model for precise biliary atresia diagnosis of infants with a single drop of blood” [Chem. Eng. J. (2026), volume 531, 1 March 2026, 173939] - Chia-Kai Lin; Chi-Ming Ku; Chia-Che Wu; Yi-Fang Wu; Huey-Ling Chen; Yueh-Ju Hou; Arnab Pal; Zong-Hong Lin; Chee-Seng Lee; Tzong-Rong Ger; Yu-Lin Wang (Chemical Engineering Journal, 2026)

Parylene-C templated synthesis of hierarchical bismuth nanoflowers for reversible chloride-ion storage - Sanjay Ballur Prasanna; Jian-Lin Lyu; Yu-Lin Lee; Ren-Jei Chung; Hong-ming Ku; Po-Chun Chen (Chemical Engineering Journal, 2026)

Structure–reactivity relationships in UV/chlorine degradation, NDMA formation, and cytotoxicity of chlorpheniramine and doxylamine - Shih-Wen Peng; Pei-Jin Lin; Ya-Hong Lin; Che-Hsin Lee; Yu-Chun Tseng; Ming-Cyuan He; Wei-Hsiang Chen (Journal of Hazardous Materials, 2026)

Effects of vacuum steam pulsed blanching on bioactive compounds, quality attributes, enzyme activities, and microstructural properties of daylily (Hemerocallis lilioasphodelus L.) - Jun Zhang; Li-Zheng Deng; Wei-Peng Zhang; Ming-Qiang Xu; You-Sheng Shi; Shi-Han Yu; Jing-Shou Zhang; Fan Yang; Shu-Lin Liu; Wei-Qiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

Microencapsulation mechanism of menthol and menthone by hydroxypropyl-β-cyclodextrin for enhanced stability and prolonged retention - Honghui Guo; Haohong Yao; Quanxing Zheng; Quanling Xie; Hongliang Lu; Xiaohua Deng; Yan Lin; Ming’en Zhang; Pengfei Ma; Zhuan Hong; Xiaoqing Huang (Food and Bioproducts Processing, 2026)

Decoupling detoxification from resource recovery: Mechanisms of organic electromigration control in bipolar membrane electrodialysis - Hao-Ran Yang; Zhi-Hua Yuan; Chang-Jiang Li; Yan-Fang Guan; Jiuyang Lin; Mohammad Younas; Xinfei Dong; Yi-Hong Jiang; Yu-Ming Zheng (Chemical Engineering Journal, 2026)

AI-driven process-tolerant BioFET sensing model for precise biliary atresia diagnosis of infants with a single drop of blood - Chia-Kai Lin; Chi-Ming Ku; Chia-Che Wu; Yi-Fang Wu; Heuy-Ling Chen; Yueh-Ju Hou; Arnab Pal; Zong-Hong Lin; Chee-Seng Lee; Tzong-Rong Ger; Yu-Lin Wang (Chemical Engineering Journal, 2026)

Mechanoluminescent Janus architecture for stimulus-responsive photodynamic therapy - Rong-Kai Du; Xu-Lin He; Qing-Qing Jin; Hong Liang; Tai-Zhong Xiao; Lei Zhong; Jun-Cheng Zhang; Tian-Ying Sun; Lei Zhou; Ming-Mei Wu (Chemical Engineering Journal, 2026)

Regulation of grain protein content by the amino acid permease gene OsAAP4 in rice - Ming-Xin Li; Feng-Lin Huang; Jin-Hong Lin; Jia-Yi Qu; Guo-Feng Wan; Gen-Cai Song; Jing Zhao; Yan Peng; Zhen-Ning Teng; Ling Liu; Cheng Zheng; Hou-Xiong Wu; et al. (Theoretical and Applied Genetics, 2026)

Psychromicrobium ferritrahens sp. nov., A Novel Actinobacterium Isolated from Decayed Wood in Shizong County, China - Lin-Bo Zhang; Jiang-Yuan Zhao; Yong-Jie Zeng; Hong-Bo Zha; Lin Gong; Pei-Wen Yang; Zhang-Gui Ding; Ming-Gang Li; Shun-Bo Gao; Le-Le Li; Shu-Kun Tang (Current Microbiology, 2026)

Dicyanoisophorone-based near-infrared fluorescent probe with a large Stokes shift for the detection and bioimaging of hydrazine - Hong-Cheng Xia; Yu-Hang Zhang; Li-Ming Lv; Di Han; Hong-Kun Yang; Hui-Juan Yan; Jie-Li Lv; Jun-Tang Lin; Ying-Ying Kong (Journal of Hazardous Materials, 2026)

Linking the occurrence, biodegradation, and N-nitrosodimethylamine formation of N,N-dimethylbenzylamine in natural waters and wastewater treatment systems - Iresha Premarathne; Yu-Lin Chen; Ya-Hong Lin; Amila Kasun Abeysinghe; Ming-Cyuan He; Wei-Hsiang Chen (Journal of Hazardous Materials, 2026)

Tuning Fe-P covalency via regenerative phosphorus vacancies for efficient aqueous cyclohexanone degradation - Han Feng; Zhengyi Lu; Ming Chen; Changming Zhong; Yongquan Wang; Rong Lin; Wenfeng Xu; Junming Hong (Environmental Research, 2026)

Differential associations of PFAS in follicular fluid and serum with reproductive hormones: Insights from a Chinese IVF cohort GIVES - Kun Zhao; Chu Chu; Michael S. Bloom; Jian-Ping Cong; Marjut Roponen; Pasi Jalava; Mo Yang; Wan-Ting He; Yun-Ting Zhang; Ming-Kun Sun; Jing-Wen Huang; Li-Xia Liang; et al. (Environmental Research, 2026)

QTL analysis of single-segment substitution lines dissected from a rice CSSL-Z668 and fine-mapping of qGL3.4 for grain length - Si-Qian Xiang; Yu-Zhu Tao; Zhao-Peng Yu; Zhuo-Wen Zhao; Han Zhang; Qiao-Long Li; Lu Li; Ao-Ni Xiang; Jing-Hong Xu; Fan Zhang; Xu Yan; Zheng-Lin Yang; et al. (Euphytica, 2026)

Highly efficient, selective, and sustainable adsorption of Nd3+ ion by amino-phosphonic acid functionalized polyacrylonitrile fibers via surface synergistic coordination - Xiao-Wei Zhang; Shuang Wang; Feng Guo; Jin-Xiu Wu; Yan-Hong Hu; Ming-Guang Chen; Rui-Lin Ren (Journal of Environmental Chemical Engineering, 2025)

Geology, isotope geochemistry and geochronology of the quartz vein-type Pb–Zn deposits in southeastern Guizhou province, SW China - Hao-Ming Deng; Yong-Yong Tang; Ya-Jiang Tian; Lin Du; Ming-Hong Zheng; Zhi-Qiang Yan; Jia-Xi Zhou; Lin Ye (Journal of Asian Earth Sciences, 2025)

Efficacy of a non-recombinant NADC34-like PRRSV-2 vaccine candidate against a recombinant NADC34-like PRRSV-2 isolate - Ming Qiu; Shuai Li; Meng Cui; Shuai Yang; Xiaoyang Zhu; Yifan Meng; Yanhan Lin; Hong Lin; Zhe Sun; Yuan Wang; Sen Jiang; Wanglong Zheng; et al. (Veterinary Microbiology, 2025)

Polycyclic aromatic hydrocarbon aggravates high-fat diet-induced metabolic dysfunction-associated steatotic liver disease through disturbing hepatocyte sphingolipid metabolism - Hui-Ru Kuo; Yu-Fen Chung; Li-Ting Wang; Chih-Wen Wang; Shih-Hsien Hsu; Li-Chen Chen; Ming-Hong Lin; Shau-Ku Huang; Kwei-Yan Liu (Environmental Pollution, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Fundamental study of horizontal wind velocity effect on PM2.5 and PM10 sampling accuracy of low-Cost sensors - Yi-Ming Lee; Thi-Cuc Le; Ying-Chang Chen; Gung-Hwa Hong; Guan-Yu Lin; Chuen-Jinn Tsai (Journal of Aerosol Science, 2025)

Rheinheimera fenheensis sp. nov., Isolated from Fenhe River Basin, China - Xuan Shao; Yun-Lin Peng; Jin-Hang Guo; Zhao-Tong Chen; Hua-Ming Zhong; Di Meng; Hong-Jian Hou; Xi-Ying Zhang; Yong Zhao; Yi Li (Current Microbiology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Unraveling the toxic trio: Combined effects of thifluzamide, enrofloxacin, and microplastics on Mytilus coruscus - Ze-Ming Zhang; Hao Liu; Hong-Lin Zuo; Yi-Nan Wang; Ai-Li Sun; Jiong Chen; Xi-Zhi Shi (Journal of Hazardous Materials, 2025)

Lactiplantibacillus plantarum GMNL-661 Ameliorates Clostridioides difficile Infection and Reconfigures Intestinal Microbiota in a Murine Model - Meng-Jia Li; Hong-Ming Chen; Yueh-Lin Chen; Yi-Hsin Lai; Cheng-Yu Lai; Jhen-Wei Ruan; Jenn-Wei Chen; Wan-Hua Tsai; Wen-Chien Ko; Pei-Jane Tsai (Probiotics and Antimicrobial Proteins, 2025)

eDNA-Based Evaluation of the Haplotypic Diversity of Orange-Spotted Grouper (Epinephelus coioides) in Stock Enhancement Areas of Wanshan Archipelago - Chun Hui Ai; Yi Long Lin; Ming Ze Chen; Jun Hong Xia (Marine Biotechnology, 2025)

Exploring possible ancient applications of perilla: evidence from 3 million fruit remains from Han Dynasty tombs in China - Yun-Jun Bai; Ming Jiang; Xue-Ping Wei; Zhi-Jun Zhao; Xin-Ying Zhou; Hong-En Jiang; Tao Xie; Xiao-Lin Li; Yu-Yang Zhao; Xue Yan; Meng Cheng; Lu-Qi Huang; et al. (Science Bulletin, 2025)

Microplastic-induced hypertension in rats: A two-hit model exploring oxidative stress and gut microbiota - Yu-Chun Cheng; Wei-Ling Chen; Hong-Ren Yu; Ching-Yi Tsai; Jiunn-Ming Sheen; Mao-Meng Tiao; Chien-Ning Hsu; You-Lin Tain (NanoImpact, 2025)

Tissue and cell types infected by Ecytonucleospora hepatopenaei (EHP) - Yuan Wang; Shi-ting Lin; Ming Zhao; Peng Di; Jun-fang Zhou; Shou-hu Li; Yan-qing Huang; Ying Na; Xin-cang Li; Wen-hong Fang (Journal of Invertebrate Pathology, 2025)

Mechanistic insights into temoporfin-based photodynamic therapy: Ferroptosis as a critical regulator under normoxic and hypoxic conditions in head and neck cancer - Tong-Hong Wang; Li-Fang Chou; Yen-Wen Shen; Nan-Chin Lin; Yin-Hwa Shih; Tzong-Ming Shieh (Journal of Photochemistry and Photobiology B: Biology, 2025)

The effect of 254 nm ultraviolet C promoting ethanol-induced gastric injury healing - A potential physical factor therapy - Xiao Zhang; Dong-mei Li; Hong-long Chen; Xi-sheng Lin; Su-su Li; Le Yu; Nan Peng; Li-kang Wang; Na Wang; Yue-ming Gao (Journal of Photochemistry and Photobiology B: Biology, 2025)

Uptake, translocation, and biotransformation of phthalate acid esters in crop plants: A comprehensive review - Nai-Xian Feng; Bogui Pan; Hong-Jia Huang; Yi-Tong Huang; Hui Lyu; Lei Xiang; Hai-Ming Zhao; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; Da-Wei Li; Ce-Hui Mo (Journal of Hazardous Materials, 2025)

Effects of novel bio-organic fertilizer on the remediation of PAEs-contaminated soil and its bacterial community composition - Hong-Jia Huang; Bogui Pan; Qi-Feng Liang; Wan-Ting Zhang; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Bai-Lin Liu; Quan-Ying Cai; Nai-Xian Feng; Ce-Hui Mo (Journal of Environmental Chemical Engineering, 2025)

Time series comparative genomics analysis reveals the adaptive evolution of caproic acid-producing bacteria to the long-term liquor brewing environment - Gan-Lin Li; Jun-Lan Mei; Li-Juan Chai; Xiao-Zhong Zhong; Ya-Ning Song; Zhen-Ming Lu; Xiao-Juan Zhang; Song-Tao Wang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (Food Bioscience, 2025)

Dynamic weather-based scheduling for achieving energy savings in factories - Kung-Yueh Camyale Chao; Yi-Ting Liu; Chia-Yi Lee; Ji-Hong Lin; Chia-Ping Cheng; Ming-Hao Lee; Hung-Chi Kuo; Tai-Jen George Chen (Energy and Buildings, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Mechanical performance and microstructure of HSLWC incorporating MWCNTs and shale-based aggregates - Qiansha Li; Jin Chai Lee; Xiaojiang Hong; Qian He; Jing Lin Ng; Wei Chek Moon; Ming Kun Yew; May Yen Chu; Bo Li (Innovative Infrastructure Solutions, 2025)

Two-photon polymerization 3D printing of biomimetic microstructures for functionalizing surfaces to inhibit bacterial growth - Wentao Zhu; Fang-Yi Huo; Lei-Ming Cao; Zi-Zhan Li; Qian Zhu; Rongxiang He; Bolei Chen; Yong Liang; Bo Cai; Hong He; Lin-Lin Bu; Ligang Hu (Chemical Engineering Journal, 2025)

Synergistic modulation of electronic structure in high entropy perovskite oxide for enhanced bifuntional oxygen evolution/reduction reactions and its mechanistic insights via in-situ analyses and density functional theory calculation - Thi Xuyen Nguyen; Chih-Heng Lee; Jun-Hong Sun; Chun-Kuo Peng; Wen-Hui Chu; Hamed Pourzolfaghar; Yu-Ru Lin; Muhammad Ghufron; Yuan-Yao Li; Yu-Hao Chang; Yan-Gu Lin; Hsin-Yi Tiffany Chen; et al. (Chemical Engineering Journal, 2025)

Comprehensive modification of cratonic lithospheric mantle beneath the central North China Craton: Insights from Li isotope systematics of olivine xenocrysts in Cenozoic basalts - Yao Xu; Hong-Fu Zhang; Yan-Jie Tang; A-Bing Lin; Juan Zhang; Ming-Jie Zhang (Chemical Geology, 2025)

ONC201 exerts oncogenic effects beyond its mitochondria-disturbing role in neuroblastoma subsets - Jyun-Hong Jiang; Yu-Han Lin; Pei-Lin Liao; Ting-Ya Chen; Hui-Ching Chuang; Chao-Cheng Huang; Wen-Ming Hsu; Jiin-Haur Chuang; Wei-Shiung Lian (Journal of Molecular Medicine, 2025)
Neuroblastoma (NB) is a formidable challenge in pediatric oncology due to its intricate molecular landscape, necessitating multifaceted therapeutic approaches. ONC201 is an imipridone antibiotic compound with a promising drug candidate leveraging its potent anticancer properties against the mitochondrial proteases ClpP and ClpX. Despite demonstrating early clinical promise, particularly in MYCN -amplified NB, its efficacy in non- MYCN -amplified NB remains a subject worthy of investigation. In this study, we extended the coverage of ONC201 to treat non- MYCN -amplified NB, and our data implicated ONC201’s inability to reduce tumor growth in animal models harboring SK-N-AS or SK-N-FI cell lines. Interestingly, ONC201 induced the expression of oncogenic markers c-Myc and LGR5 while downregulating the tumor suppressor ATRX. While it fails to attenuate tumor neovascularization in non- MYCN -amplified NB xenografts, its effectiveness differs from that of its MYCN-amplified counterpart. Rho zero (ρ0)-SK-N-AS cells treated with ONC201 showed comparable observed trends in parental SK-N-AS cells, including LGR5 upregulation and ATRX downregulation, suggesting that ONC201’s multifaceted actions extend beyond mitochondrial targets. Our elucidation highlights the need to discern molecular signatures when deploying ONC201 monotherapy against NB, which lacks MYCN- amplification.

Small intestine-residing probiotics suppress neurotoxic bile acid production via extracellular vesicle-mediated inhibition of Clostridium scindens - Wei-Leng Chin; Bao-Hong Lee; Qiao-Yu Hsu; Chih-Yao Hou; Ming-Chyi Pai; Chi-Wei Lin; Wei-Hsuan Hsu (Food Research International, 2025)

Efficient conversion and highly sensitive detection of PAEs in milk based on hydrazinolysis reaction and hydrogen bonding using SERS technique - Lili Hua; Hongmei Li; Jing-Wen Zhou; Xiao-Feng Liu; Xian-Ming Guo; Zhao-Bing Zhang; Yichuan Kou; Tang-Tang Xie; Cuihong Sheng; Lin Zhang; Sheng-Hong Liu; Fan-Li Zhang; et al. (Analytica Chimica Acta, 2025)

What does it mean when the pleasant smells come and go? Correlation between UPSIT odor identification status and fluctuation of non-motor symptoms in Parkinson’s disease - Hsin-Bei Lei; Ting-Chun Fang; Yu-Hsuan Lin; Shih-Chi Chiu; Ming-Hong Chang; Yi-Jen Guo (Acta Neurologica Belgica, 2025)
Parkinson’s disease (PD) is characterized by motor and non-motor symptoms, including olfactory dysfunction. Prior studies have shown that olfaction deteriorates with disease progression, however fluctuations in olfaction and related PD symptoms have been less explored. This study aimed to investigate correlations between changes in odor identification ability and PD symptoms. PD patients recruited from Taichung Veterans General Hospital underwent at least two consecutive Movement Disorder Society Unified Parkinson’s Disease Rating Scale (MDS-UPDRS) and University of Pennsylvania Smell Identification Test (UPSIT) evaluations. The patients were grouped based on changes in olfactory identification ability between evaluations, and fluctuations in PD symptoms were compared between groups. Ninety-seven PD patients with 114 complete sets of data were analyzed. Significant divergent results were observed between changes in five MDS-UPDRS non-motor subscores and the conversion status of five pleasant odors, including anxiety vs. bubble gum, apathy vs. banana, dizziness vs. coconut, urination vs. root beer, and dopamine dysregulation syndrome (DDS) vs. grape. Fluctuations in the ability to detect pleasant odors, may have a complex interaction with other non-motor symptoms, including in the neurobehavioral and autonomic domains. Serial monitoring of olfactory function, particularly with pleasant odors, may provide valuable insights for tracking non-motor symptoms in PD and warrants further investigation into their therapeutic implications.

Cumulus cells and the TNF-alpha signaling facilitate aging of ovine oocytes - Shuai Gong; Yan Zhang; Chao-Qun Cong; Guo-Liang Wang; Lin Jiang; Hong-Jie Yuan; Jing-He Tan; Ming-Jiu Luo (Theriogenology, 2025)

Extensive cytonuclear discordance revealed by phylogenomic analyses suggests complex evolutionary history in the holly genus Ilex (Aquifoliaceae) - Ke-Wang Xu; Yi Yang; Hong Chen; Chen-Xue Lin; Lei Jiang; Zhong-Long Guo; Meng Li; Ming-Zhuo Hao; Kai-Kai Meng (Molecular Phylogenetics and Evolution, 2025)

Microbial augmented aerobic composting for effective phthalates degradation in activated sludge - Bogui Pan; Hong Tian; Qi-Feng Liang; Hong-Jia Huang; Yi-Tong Huang; Bai-Lin Liu; Yan-Wen Li; Lei Xiang; Hai-Ming Zhao; Quan-Ying Cai; Nai-Xian Feng; Ce-Hui Mo (Journal of Environmental Management, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Growth, biochemical indexes, and intestinal microbiota response of red tilapia (Oreochromis spp.) under different densities and feeding frequencies in the land-based aquaculture tank - Yu-Xiang Xie; Jun-Neng Liang; Gen Kaneko; Lu-Ting Wen; Yi-Jian Li; Qui-Wei Ao; Li-Ming Huang; Qiong Yang; Zhen-Ping Liao; Xue-Ming Yang; Hong-ping Zhang; Lin-Yuan Jiang; et al. (Aquaculture, 2025)

The replication efficacy of NADC34-like porcine reproductive and respiratory syndrome virus 2 is not directly associated with the pathogenicity - Meng Cui; Ming Qiu; Shuai Yang; Yuejia Qiu; Wenhao Qi; Hong Lin; Zhe Sun; Wanglong Zheng; Jianzhong Zhu; Nanhua Chen (Veterinary Microbiology, 2025)

Acidosis induces autophagic cell death through ASIC1-mediated Akt/mTOR signaling in HT22 neurons - Miao Guo; Ming-Yue Qiu; Lin Zeng; Ya-Xiong Nie; Ya-Ling Tang; Yan Luo; Hong-Feng Gu (Toxicology, 2025)

The characterization of zein/xanthan gum composite oleogel: A comparative study of bioactive substances in interface and oil phases - Hong Chen; Qiming Wang; Sili Liu; Zhenan Rao; Xiaojuan Lei; Jichun Zhao; Lin Lei; Kaihong Zeng; Jian Ming (Food Hydrocolloids, 2025)

A super convenient and specific CRISPR/Cas12a diagnostic platform for toxigenic Burkholderia gladioli based on virulence genes - Yu Xie; Li Liu; Xue-Ming Cao; Zuo-Qi Gai; Xu Zhang; Hong-Tao Lei; Zhen-Lin Xu; Xing Shen (Food Control, 2025)

Mechanisms of immune responses in Acanthopagrus latus to Streptococcus agalactiae infection revealed by transcriptomic analysis - Hong-Di Fan; Yuan-Ming Zhao; Min Liu; Xu Wang; Jia Lin; Wen Huang; Jiang-Hai Wang (Fish & Shellfish Immunology, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Year-round natural spawning, early ontogeny, and larval rearing of the painted sweetlips, Diagramma pictum (Thunberg, 1792) in a hatchery: Potential as a new species for mariculture - Pei-Sheng Chiu; Bo-Hong Yu; Yu-Hsin Tu; Yeong-Torng Chu; Cheng-Hsuan Huang; Shine-Wei Ho; Sun-Hon Lin; Shinn-Lih Yeh; Ming-Yih Leu (Aquaculture, 2025)

A boundary enforcement method for the truncated ship structure model during underwater contact explosion experiments - Liang Zhang; Xin Lin; Hong-Na Yang; Fu-Ren Ming (Ocean Engineering, 2025)

Bioconversion of agriculture by-products with functionally enhanced Streptomyces sp. SCUT-3: Fish skin as a model - Jing-Tao Ni; Ming-Shu Zhang; De-lin Lu; Wen-jun Lu; Lei Wu; Zhen-dong Yang; Can Qin; Zhen-jie Dai; Zhi-wei Li; Wen-jing Feng; Hua-hong Cai; Jia-rui Zhang; et al. (Food Chemistry, 2025)

Revealing the links between hair metal(loids) and alterations in blood pressure among children in e-waste recycling areas through urinary metabolomics - Hong-Xuan Kuang; Ye Liu; Jia-Rong Wang; Meng-Yang Li; Yang Zhou; Lin-Xue Meng; Ming-Deng Xiang; Yun-Jiang Yu (Science of The Total Environment, 2024)

Numerical examination of wave forces on partially submerged horizontal circular cylinders near free surface - Hong-Fei Mao; Yuan-Ting Yang; Jin-Bo Lin; Zhong-Bing Zhou; Ming He (Ocean Engineering, 2024)

Calcium regulates the physiological and molecular responses of Morus alba roots to cadmium stress - Ming-Jin Dai; Lu-Dan Zhang; Jing Li; Chun-Quan Zhu; Ling-Yu Song; He-Zi Huang; Chao-Qun Xu; Qing-Hua Li; Lin Chen; Chen-Kai Jiang; Hong-Ling Lu; Qiu-Tong Ling; et al. (Journal of Hazardous Materials, 2024)

Associations between multiple metals exposure and cognitive function in the middle-aged and older adults from China: A cross-sectional study - Shiru Hong; Sheng Wu; Zhengce Wan; Chenming Wang; Xin Guan; Ming Fu; Chenliang Liu; Tianhao Wu; Guorong Zhong; Yuhan Zhou; Yang Xiao; Yingqian You; et al. (Environmental Research, 2024)

A zircon petrochronologic perspective on raising the central Tibetan crust - Shu-Hui Ren; Yun-Chuan Zeng; Roberto Weinberg; Ji-Feng Xu; Jian-Lin Chen; Bao-Di Wang; Feng Huang; Xi-Jun Liu; Hong-Xia Yu; Ming-Jian Li (Chemical Geology, 2024)

Increase of PCSK9 expression in diabetes promotes VEGFR2 ubiquitination to inhibit endothelial function and skin wound healing - Jian-Jun Gao; Fang-Yuan Wu; Yu-Jia Liu; Le Li; Yi-Jun Lin; Yue-Ting Kang; Yue-Ming Peng; Yi-Fang Liu; Chen Wang; Zhen-Sheng Ma; Yang Cao; Hong-Yu Cao; et al. (Science China Life Sciences, 2024)

Alendronate sodium induces G1 phase arrest and apoptosis in human umbilical vein endothelial cells by inhibiting ROS-mediated ERK1/2 signaling - Yi Feng; Shao-Qin Tu; Yu-Luan Hou; Yi-Ting Shao; Lin Chen; Zhi-Hui Mai; Yu-Xuan Wang; Jia-Ming Wei; Sai Zhang; Hong Ai; Zheng Chen (Toxicology, 2024)

Planting halophytes increases the rhizosphere ecosystem multifunctionality via reducing soil salinity - Jin-Peng Hu; Yuan-Yuan He; Jian-Hong Li; Zhao-Long Lü; Yue-Wei Zhang; Yuan-Hong Li; Jia-Lü Li; Ming-Xu Zhang; Yan-Hua Cao; Jin-Lin Zhang (Environmental Research, 2024)

Gel electrolyte design for nonflammable lithium-ion batteries with high-rate and high-voltage characteristics - Po-Wei Huang; Qin-Cheng Zhang; Ming-Yuan Hung; Yan-Cheng Lin; Hong-Kang Tian; Yuh-Lang Lee; Jeng-Shiung Jan; Hsisheng Teng (Chemical Engineering Journal, 2024)

Fabrication of flexible Co3Fe7@Ti3C2Tx/TiO2/C@Spacer fabrics for tunable radar-infrared compatible stealth Inspired by layered structure of rock - Jiatong Yan; Chuanxi Lin; Shan Jiang; Weijie Wang; Ming Zhong; Hong Tang; Ronghui Guo (Chemical Engineering Journal, 2024)

Dual-Salt aqueous electrolyte for enhancing Charge-Storage properties of VO2 polymorphic cathodes for Zn-Ion batteries - Jing-Hong Huang; Xu-Feng Luo; Tzu-Yu Kuo; Yu-Hua Lai; Purna Chandra Rath; Chun-Wei Huang; Ming-Hsien Lin; An-Yuan Hou; Ju Li; Yu-Sheng Su; Wen-Wei Wu; Jeng-Kuei Chang (Chemical Engineering Journal, 2024)

A Cysteinyl-tRNA Synthetase Mutation Causes Novel Autosomal-Dominant Inheritance of a Parkinsonism/Spinocerebellar-Ataxia Complex - Han-Kui Liu; Hong-Lin Hao; Hui You; Feng Feng; Xiu-Hong Qi; Xiao-Yan Huang; Bo Hou; Chang-Geng Tian; Han Wang; Huan-Ming Yang; Jian Wang; Rui Wu; et al. (Neuroscience Bulletin, 2024)
This study aimed to identify possible pathogenic genes in a 90-member family with a rare combination of multiple neurodegenerative disease phenotypes, which has not been depicted by the known neurodegenerative disease. We performed physical and neurological examinations with International Rating Scales to assess signs of ataxia, Parkinsonism, and cognitive function, as well as brain magnetic resonance imaging scans with seven sequences. We searched for co-segregations of abnormal repeat-expansion loci, pathogenic variants in known spinocerebellar ataxia-related genes, and novel rare mutations via whole-genome sequencing and linkage analysis. A rare co-segregating missense mutation in the CARS gene was validated by Sanger sequencing and the aminoacylation activity of mutant CARS was measured by spectrophotometric assay. This pedigree presented novel late-onset core characteristics including cerebellar ataxia, Parkinsonism, and pyramidal signs in all nine affected members. Brain magnetic resonance imaging showed cerebellar/pons atrophy, pontine-midline linear hyperintensity, decreased rCBF in the bilateral basal ganglia and cerebellar dentate nucleus, and hypo-intensities of the cerebellar dentate nuclei, basal ganglia, mesencephalic red nuclei, and substantia nigra, all of which suggested neurodegeneration. Whole-genome sequencing identified a novel pathogenic heterozygous mutation (E795V) in the CARS gene, meanwhile, exhibited none of the known repeat-expansions or point mutations in pathogenic genes. Remarkably, this CARS mutation causes a 20% decrease in aminoacylation activity to charge tRNA Cys with L-cysteine in protein synthesis compared with that of the wild type. All family members carrying a heterozygous mutation CARS (E795V) had the same clinical manifestations and neuropathological changes of Parkinsonism and spinocerebellar-ataxia. These findings identify novel pathogenesis of Parkinsonism-spinocerebellar ataxia and provide insights into its genetic architecture.

Analysis of growth inhibition of continuously planted Casuarina equisetifolia in relation to characteristic soil microbial functions and nutrient cycling - Yu-Hua Wang; Lei Hong; Jian-Juan Li; Qing-Xu Zhang; Ai-Qi Wang; Shao-Xiong Lin; Ming-Yue Hu; Yi-Ling Chen; Wen-Xiong Lin; Hai-Bin Wang; Ze-Yan Wu (Applied Soil Ecology, 2024)

CXCR3 participates in asymmetric division of mouse oocytes by modulating actin dynamics - Wei-jian Li; Rong-yang Li; Da-yu Wang; Ming Shen; Hong-lin Liu (Theriogenology, 2024)

Association of prenatal multiple metal exposures with child neurodevelopment at 3 years of age: A prospective birth cohort study - Yun Qiu; Yuxin Liu; Ming Gan; Weiting Wang; Tao Jiang; Yangqian Jiang; Hong Lv; Qun Lu; Rui Qin; Shiyao Tao; Lei Huang; Xin Xu; et al. (Science of The Total Environment, 2024)

Biocontrol potential of Bacillus velezensis QF-2 isolated from rhizosphere soil of Vickifunkia tianschanica - Tong Shen; Lei Zhang; Zhi-Han Ma; Zheng Gong; Hui-Ming Qi; Hong-Ying Yang; Yi-Lin He (Physiological and Molecular Plant Pathology, 2024)

Integrated membrane process of tubular ultrafiltration-nanofiltration-electrodialysis-reverse osmosis for treating fracturing flowback fluid - Bing Xu; Qian Zhang; Huanhuan Wu; Qianqian Tian; Wenming Chai; Ming Zhang; Guangyi Shao; Shuwen Tian; Yakai Lin; Hong Yao (Journal of Cleaner Production, 2024)

Establishment of a callus induction system of Saxifraga stolonifera Meerb. and its response to different elicitors - Lin Song; Ta Zhao; Chun-Li Luo; Jin-Ling Li; Song-Shu Chen; Dan-Dan Li; Jin Liang; Hong-Chang Liu; Fu-Lai Luo; Ming-Jin Huang; Hua-Lei Wang (South African Journal of Botany, 2024)

The role of Pleistocene dispersal in shaping species richness of sky island wintergreens from the Himalaya-Hengduan Mountains - Xiao-Juan Cheng; Peter W. Fritsch; Yan-Jun Lin; Guo-Hong Li; Yan-Quan Chen; Ming-Ying Zhang; Lu Lu (Molecular Phylogenetics and Evolution, 2024)

Metals/bisulfite system involved generation of 24-sulfonic-25-ene ginsenoside Rg1, a potential quality control marker for sulfur-fumigated ginseng - Hui Liu; Xiao-Qian Wu; Xiang-Ling Qin; Jin-Hao Zhu; Jin-Di Xu; Shan-Shan Zhou; Ming Kong; Hong Shen; Jie-Ge Huo; Song-Lin Li; He Zhu (Food Chemistry, 2024)

Influence of geological uncertainty on longitudinal deformation of tunnel based on improved coupled Markov chain - Qi-Hao Jiang; Jin-Zhang Zhang; Dong-Ming Zhang; Hong-Wei Huang; Jing-Kang Shi; Zhang-Lin Li (Engineering Geology, 2024)

Prevalence and molecular characterization of Cryptosporidium spp., Enterocytozoon bieneusi, and Giardia duodenalis in dairy cattle in Ningxia, northwestern China - Ming-Yuan Wang; Shan Zhang; Zhan-Sheng Zhang; Xiao-Yin Qian; Hai-Liang Chai; Yan Wang; Wen-Jun Fan; Chao Yi; Yu-Lin Ding; Wen-Xiong Han; Li Zhao; Yong-Hong Liu (Veterinary Research Communications, 2024)

Actin-related protein MoFim1 modulated the pathogenicity of Magnaporthe oryzae by controlling three MAPK signaling pathways, appressorium formation, and hydrophobicity - Yun-Yun Wei; Xue-Ming Zhu; Xiao-Hong Liu; Fu-Cheng Lin; Shuang Liang (Physiological and Molecular Plant Pathology, 2024)

Differential effects of oxytetracycline on detoxification and antioxidant defense in the hepatopancreas and intestine of Chinese mitten crab under cadmium stress - Lin Zeng; Yong-Hong Wang; Chun-Xiang Ai; Bin Zhang; Hui Zhang; Zi-Ming Liu; Min-Hui Yu; Bing Hu (Science of The Total Environment, 2024)

Exploring the chemical diversity of sesquiterpenes from the rarely studied south China sea soft coral Sinularia tumulosa assisted by molecular networking strategy - Sheng-Hui Zhu; Yuan-Min Chang; Song-Wei Li; Ming-Zhi Su; Li-Gong Yao; Lin-Fu Liang; Hong Wang; Yue-Wei Guo (Phytochemistry, 2024)

Pleurotus eryngii root waste and soybean meal co-fermented protein improved the growth, immunity, liver and intestinal health of largemouth bass (Micropterus salmoides) - Jian-Ming Xu; Wen-Rong Gao; Ping Liang; Guo-He Cai; Hong-Ling Yang; Jian-Bin Lin; Yun-Zhang Sun (Fish & Shellfish Immunology, 2024)

Environmentally relevant concentrations of benzophenones exposure disrupt intestinal homeostasis, impair the intestinal barrier, and induce inflammation in mice - Yu-Jia Lin; Hong-Mei Li; Yan-Rong Gao; Ping-Fan Wu; Bin Cheng; Chen-Long Yu; Yu-Xin Sheng; Hai-Ming Xu (Environmental Pollution, 2024)

CuO NWs boosted triboelectric microfluidic nanosensor functionalized by collagen-protein interactions for real-time platelet count monitoring - Jia-Cheng Lin; Kuldeep Kaswan; Subhodeep Chatterjee; Yu-Wen Wu; Manish Kumar Sharma; Ashok Ranjan; Snigdha Roy Barman; Yu-Zih Lin; Thierry Burnouf; Wilfrid Boireau; Ming-Yen Lu; Yong-Kwang Tu; et al. (Chemical Engineering Journal, 2024)

Antiproliferative polycyclic polyprenylated acylphloroglucinols from Garcinia paucinervis - Cui-Cui Jia; Jing-Jing Xue; Zhan-Lin Li; Da-Hong Li; Hui-Ming Hua (Natural Product Research, 2024)

Medial amygdala NRG1 signaling mediates adolescent social isolation-induced autistic-like behaviors - Lian-Hong Lin; Qian-Yun Wu; Kai Zeng; Zi-Yu Chen; Zi-Ping Wang; Wei-Min Li; Bin Zhang; Tian-Ming Gao; Ji-Hong Liu (Science Bulletin, 2024)

Inhibition of PARP1 improves cardiac function after myocardial infarction via up-regulated NLRC5 - Jia-Ming Luo; Hong-Bin Lin; Ya-Qian Weng; Ying-Hui Lin; Lu-Ying Lai; Ji Li; Feng-Xian Li; Shi-Yuan Xu; Hong-Fei Zhang; Wei Zhao (Chemico-Biological Interactions, 2024)

Correction to: BMP2 induces chondrogenic differentiation, osteogenic differentiation and endochondral ossification in stem cells - Nian Zhou; Qi Li; Xin Lin; Ning Hu; Jun-Yi Liao; Liang-Bo Lin; Chen Zhao; Zhen-Ming Hu; Xi Liang; Wei Xu; Hong Chen; Wei Huang (Cell and Tissue Research, 2024)

Endothelin-1-mediated Brainstem Glial Activation Produces Asthmatic Airway Vagal Hypertonia Via Enhanced ATP-P2X4 Receptor Signaling in Sprague–Dawley Rats - Yun Lin; Tian Liu; Hong Chen; Ming Zeng; Shunwei Hu; Xiaoning Yu; Yonghua Chen; Chunmei Xia; Jin Wang; Jijiang Wang (Journal of Neuroimmune Pharmacology, 2024)

Arsenic effectively improves the degradation of fluorene by Rhodococcus sp. 2021 under the combined pollution of arsenic and fluorene - Hong-Peng Shi; Ying-Hao Zhao; Mei-Lin Zheng; Cheng-Yan Gong; Lei Yan; Ying Liu; Yong-Ming Luo; Zhi-Pei Liu (Chemosphere, 2024)

Structurally diverse cucurbitane-type triterpenoids from the tubers of Hemsleya chinensis with cytotoxic activity - Xiao-San Li; Qi-Lin Wang; Zhi-Peng Xu; Ming-Shang Liu; Xiao-Yan Liang; Jia-Chon Zheng; Hong-Yao Deng; Li Liu; Yong-Mei Huang; Mao-Xun Yang; Xue-Mei Yang (Phytochemistry, 2024)

Non-fitting functional representation for the equilibrium constant subject to reaction between H2S and CO2 - Chao-Wen Wang; Ji Li; Lie-Hui Zhang; Qun-Chao Ding; Guan-Hong Liu; Gao Li; Rui Jiang; Xiao-Long Peng; Lin-Sheng Wei; Hong-Ming Tang; Jian-Yi Liu; Chun-Sheng Jia (Fuel, 2024)

SERS lateral flow strip detection of serum biomarkers for noninvasive assessment of operative microwave ablation outcomes of unresectable hepatocellular carcinoma - Xiaoming Su; Xinyu Liu; Yuzhen Ouyang; Yangcenzi Xie; Mingyang Chen; Pan Chen; Jia Liu; Minghua Wu; Chien-hong Lin; Hong Zhong; Ming Li (Chemical Engineering Journal, 2024)

Environmental exposure to per- and polyfluoroalkyl substances mixture and asthma in adolescents - Yi-Fan Wang; Li Li; Xu Wang; Ya-Nan Yun; Xue-Lin Wang; En-Yang He; Ming-Kun Song; Xue-Hong Xia; Ying-Xue Zou (International Archives of Occupational and Environmental Health, 2024)

Rational tuning of binding properties of pillar [5] arene-based sensing material by synergistic effect and its application for fluorescent turn-on detection of isoniazid and controlled reversible morphology - Jian-Peng Hu; Qi Zhao; Qi Lin; Hong Yao; You-Ming Zhang; Tai-Bao Wei (Analytica Chimica Acta, 2024)

Identifying the source and fate of boron in geothermal water: Evidence from B/Na and B isotopes - Ying Tan; Xiao-Wei Jiang; Tao-Tao Ji; Yin-Fei Luo; Wan Dai; Hong Zhang; Zhao-Xuan Niu; Yu-De Lei; Zhi-Yuan Zhang; Tian-Yi Lin; Hua-Ming Guo (Science of The Total Environment, 2024)

Neurological impairment is crucial for tire rubber-derived contaminant 6PPDQ-induced acute toxicity to rainbow trout - Xiao-Liang Liao; Zhi-Feng Chen; Shi-Ping Ou; Qian-Yi Liu; Shan-Hong Lin; Jia-Ming Zhou; Yujie Wang; Zongwei Cai (Science Bulletin, 2024)

Perturbation of lipid metabolism in 3T3-L1 at different stages of preadipocyte differentiation and new insights into the association between changed metabolites and adipogenesis promoted by TBBPA or TBBPS - Yun-Jiang Yu; Jing-Lin Tian; Tong Zheng; Hong-Xuan Kuang; Zong-Rui Li; Chao-Jie Hao; Ming-Deng Xiang; Zhen-Chi Li (Journal of Hazardous Materials, 2024)

Influence on the volatilization of ethyl esters: Nonnegligible role of long-chain fatty acids on Baijiu flavor via intermolecular interaction - Qing-Ru Liu; Xian-Li Lin; Zhen-Ming Lu; Li-Juan Chai; Song-Tao Wang; Jin-Song Shi; Su-Yi Zhang; Cai-Hong Shen; Xiao-Juan Zhang; Zheng-Hong Xu (Food Chemistry, 2024)

Leaching and evolution of anthocyanins and aroma compounds during Cabernet Sauvignon wine fermentation with whole-process skin-seed contact - Xue-Chen Yao; Hua-Lin Zhang; Xin-Rui Ma; Nong-Yu Xia; Chang-Qing Duan; Wei-Ming Yang; Qiu-Hong Pan (Food Chemistry, 2024)

Characterization of spatial-temporal distribution and microenvironment source contribution of PM2.5 concentrations using a low-cost sensor network with artificial neural network/kriging techniques - Yi-Ming Lee; Guan-Yu Lin; Thi-Cuc Le; Gung-Hwa Hong; Shankar G. Aggarwal; Jhih-Yuan Yu; Chuen-Jinn Tsai (Environmental Research, 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

Stalemate or consensus? Evolution of stakeholders’ behavioral strategies in construction land reduction in China - Jia-He Zhou; Yu-Ming Zhu; Cai-Hong Liu; Lei He; Hong-Li Lin (Environment, Development and Sustainability, 2024)

Adsorption effect and mechanism of Cd(II) by different phosphorus-enriched biochars - Yang Zeng; Yuhan Lin; Ming Ma; Hong Chen (Environmental Science and Pollution Research, 2024)

PD-L1 expression guidance on sintilimab versus pembrolizumab with or without platinum-doublet chemotherapy in untreated patients with advanced non-small cell lung cancer (CTONG1901): A phase 2, randomized, controlled trial - Si-Yang Maggie Liu; Jie Huang; Jia-Yi Deng; Chong-Rui Xu; Hong-Hong Yan; Ming-Yi Yang; Yang-Si Li; E-E Ke; Ming-Ying Zheng; Zhen Wang; Jia-Xin Lin; Bin Gan; et al. (Science Bulletin, 2024)

Anthropogenic nitrogen pollution inferred by stable isotope records of crustose coralline algae - Aafaq Nazir; Chiao-Feng Lai; Shih-Wei Wang; Showe-Mei Lin; Hong-Chun Li; Ming-Tsung Chung; Pei-Ling Wang; Yung-Che Tseng; Jen-Chieh Shiao (Marine Pollution Bulletin, 2024)

Aridity drives the variability of desert soil microbiomes across north-western China - Lei Dong; Mei-Xiang Li; Shuai Li; Ling-Xiang Yue; Mukhtiar Ali; Jia-Rui Han; Wen-Hui Lian; Chao-Jian Hu; Zhi-Liang Lin; Guo-Yuan Shi; Pan-Deng Wang; Shao-Ming Gao; et al. (Science of The Total Environment, 2024)

Reconstruction of microcontinents during the assembly of Rodinia: A case study from the Central Tianshan Block - Lin-Xi Wang; Hu Huang; Ming-Cai Hou; Benjamin Kneller; Fu-Hao Xiong; Hong-Wei Luo; Sheng-Xian Zhu (Precambrian Research, 2024)

Expression of polyphenol oxidase of Litopenaeus vannamei and its characterization - Qian Hong; Yu-Lei Chen; Duanquan Lin; Ru-Qing Yang; Kai-Yuan Cao; Ling-Jing Zhang; Yi-Ming Liu; Le-Chang Sun; Min-Jie Cao (Food Chemistry, 2024)

Water turbidity dynamics using random forest in the Yangtze River Delta Region, China - Xingna Lin; Ming Wu; Xuexin Shao; Guozhi Li; Yifeng Hong (Science of The Total Environment, 2023)

Remediation of diesel-oil contaminated soils using an innovative nanobubble and electrolyzed catalytic system - Wei-Ting Chen; Justin Chun-Te Lin; Shih-Hsiung Chen; Francis Verpoort; Kun-Liang Hong; Rao Y. Surampalli; Chih-Ming Kao (Journal of Cleaner Production, 2023)

Application of novel nanobubble-contained electrolyzed catalytic water to cleanup petroleum-hydrocarbon contaminated soils and groundwater: A pilot-scale and performance evaluation study - Wing-Sze Ho; Wei-Han Lin; Francis Verpoort; Kun-Liang Hong; Jiun-Hau Ou; Chih-Ming Kao (Journal of Environmental Management, 2023)

Yuexiconcha nov. gen. – A resilifer-bearing palaeotaxodont (Bivalvia, Protobranchia) from the Ordovician of Guangdong, South China - Zhi-jun Niu; Ren-jie Zhang; Paul A. Johnston; Chu-an Li; Zhi-hong Wang; Kun Hu; Fang Song; Yao-yan He; Jin-lan He; Xiao-ming Lin; Wen-qiang Yang (Geobios, 2023)

The linear/nonlinear rheological behaviors of Pickering emulsion stabilized by Zein and Xanthan gum: Effect of interfacial assembly strategies - Hong Chen; Qiming Wang; Zhenan Rao; Xiaojuan Lei; Jichun Zhao; Lin Lei; Jian Ming (Food Hydrocolloids, 2023)

Characteristics and Geological Significance of High-precision Aeromagnetic Data in LinFen-YunCheng - Ming Wang; Jin-hong Qu; Xiao-xing Lin; Zhen-jun Liu; Fang Li (Applied Geophysics, 2023)

Numerical Investigation on Hydrodynamic Characteristics and Drag Influence of an Open-Frame Remotely Operated Underwater Vehicle - Desheng Zhang; Xin Wang; Ming Zhao; Lin Hong; Xuecheng Li (Journal of Marine Science and Engineering, 2023)
Remotely operated underwater vehicles (ROVs) have been widely used in deep-sea resource exploitation and industrial engineering operations. To perform these tasks accurately in the deep-sea environment, stable motion control has become a key area of research on ROV systems, which has led to the importance of analyzing the hydrodynamic characteristic of ROVs. But a systematic methodology for analyzing the hydrodynamic characteristics of ROVs is still lacking nowadays. In this paper, systematic numerical simulation methods for analyzing hydrodynamic characteristics and shape optimization of a work-class ROV are conducted, and details of simulation procedures based on computational fluid dynamics are studied, which can be a foundation for robust controller design.

Sulforaphane alleviates the meiosis defects induced by 3-nitropropionic acid in mouse oocytes - Wei-Jian Li; Xuan Zhang; Ming Shen; Hong-Lin Liu; Li-Ren Ding (Food and Chemical Toxicology, 2023)

Risk assessment of mountain tourism on the Western Sichuan Plateau, China - Yu-Qing Zhang; Yue-Lin Wang; Hong Li; Xue-Ming Li (Journal of Mountain Science, 2023)

Extended exposure to tetrabromobisphenol A-bis(2,3-dibromopropyl ether) leads to subfertility in male mice at the late reproductive age - Yuan-Yuan Li; Yi-Ming Xiong; Xuan-Yue Chen; Jia-Yi Sheng; Lin Lv; Xing-Hong Li; Zhan-Fen Qin (Archives of Toxicology, 2023)

Paternal lipopolysaccharide exposure induced intrauterine growth restriction via the inactivation of placental MEST/PI3K/AKT pathway in mice - Pei-Ying Jiang; Shuai Lin; Jie-Ru Liu; Yan Liu; Li-Ming Zheng; Qiang Hong; Yi-Jun Fan; De-Xiang Xu; Yuan-Hua Chen (Archives of Toxicology, 2023)

Acoustic Field Radiation Prediction and Verification of Underwater Vehicles under a Free Surface - Yung-Wei Chen; Cheng-Cheng Pan; Yi-Hsien Lin; Chao-Feng Shih; Jian-Hong Shen; Chun-Ming Chang (Journal of Marine Science and Engineering, 2023)
This study aimed to examine the acoustic field radiated by propellers and underwater vehicles. For the verification of sound radiation in underwater vehicles, numerical methods are widely used in addition to experiments and propeller blade frequencies for calculation and validation. Numerical convergence and accuracy are more important for near-field and far-field problems. This paper uses the boundary element method (BEM) to assess the convergence of the finite volume method (FVM). In this study, the FVM, including the Reynolds-averaged Navier–Stokes method and the Ffowcs Williams–Hawkings (FW-H) acoustic model, is used to investigate the influence of various geometric inflows on the hydrodynamic and noise performance of the propeller. Then, the sound radiation of the FVM is compared with the BEM at the far field to determine the number of meshed elements. Furthermore, spectral analysis is being conducted to examine the noise generated by the underwater vehicle and propeller. The objective is to investigate the influence of the free surface on propeller efficiency. After verifying the numerical simulation, the results indicate that a relationship can be established between water pressure and propeller thrust under specific conditions. This relationship can be used to estimate the magnitude of propeller thrust at different water depths. The simulated results of propeller thrust, torque coefficient, propulsion efficiency, and sound radiation in this study are consistent with experimental values. This demonstrates the accuracy and practicality of the findings of numerical procedures in engineering applications.

Efficacy of a porcine reproductive and respiratory syndrome virus 1 (PRRSV-1) natural recombinant against a heterologous PRRSV-1 isolate both clustered within the subgroup of BJEU06-1-like isolates - Chen Li; Shuai Li; Shubin Li; Ming Qiu; Hong Lin; Zhe Sun; Yuejia Qiu; Wenhao Qi; Binghui Feng; Jixiang Li; Wanglong Zheng; Xiuling Yu; et al. (Veterinary Microbiology, 2023)

Towards effective recovery of humate as green fertilizer from landfill leachate concentrate by electro-neutral nanofiltration membrane - Wenyuan Ye; Mingqiu Hong; Xuan Huang; Tianci Chen; Ailiang Gu; Xiaocheng Lin; Xuewei Li; Xiangrong Chen; Dong Han Seo; Shuaifei Zhao; Xueming Chen; Bart Van der Bruggen; et al. (Science of The Total Environment, 2023)

Integrated MOVES model and machine learning method for prediction of CO2 and NO from light-duty gasoline vehicle - Run Liu; Hong-di He; Zhe Zhang; Cui-lin Wu; Jin-ming Yang; Xing-hang Zhu; Zhong-ren Peng (Journal of Cleaner Production, 2023)

Biodegradable micro-nanofiber medical tape with antibacterial and unidirectional moisture permeability - Ning Zhou; Yu-Fei Gao; Ying Huo; Kai Zhang; Jian Zhu; Ming-Yi Chen; Ling Zhu; Yi-Hang Dong; Hong-Guo Gao; Ick Soo Kim; Ke-Qin Zhang; Rou-Xi Chen; et al. (Chemical Engineering Journal, 2023)

High-performance peptide and disulfide mapping by direct injection of intact proteins using on-line coupled UV-liquid chromatography microdroplet mass spectrometry (UVLC-MMS) - Chin-Ming Kuo; Hung-Hsiang Jen; Fung-Yu Chen; Mohsen Akbarian; Tai-Hong Ou; Kang-Yu Liu; Jung-Lee Lin; Shu-Hui Chen (Analytica Chimica Acta, 2023)

Metformin improves sheep sperm cryopreservation via vitalizing the AMPK pathway - Xing Zhang; Song-Mao Guo; Da-Wei Zhu; Yu Li; Fei Wen; Ming Xian; Zhang-Tao Hu; Qian-Long Zou; Li-Kun Zhang; Yu-Lin Chen; Jian-Hong Hu (Theriogenology, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Dual-modular immunosensor for bongkrekic acid detection using specific monoclonal antibody - Xue-Ming Cao; Li-Hua Li; Hong-Zhi Liang; Jia-Dong Li; Zi-Jian Chen; Lin Luo; Yi-Na Lu; Yu-Xin Zhong; Yu-Dong Shen; Hong-Tao Lei; Hong Wang; Zhen-Lin Xu (Journal of Hazardous Materials, 2023)

Rational design of surface reconstruction with pinning effect to relieving bulk fatigue for high energy single-crystal Ni-rich cathodes - Ying-de Huang; Han-Xin Wei; Pei-Yao Li; Lin-Bo Tang; Yu-Hong Luo; Xin-Ming Fan; Cheng Yan; Jing Mao; Ke-Hua Dai; He-Zhang Chen; Xia-hui Zhang; Jun-chao Zheng (Chemical Engineering Journal, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Neuron-Derived Exosomes Promote the Recovery of Spinal Cord Injury by Modulating Nerve Cells in the Cellular Microenvironment of the Lesion Area - Yi Xu; Zheng-huan Zhu; Xu Xu; Hai-tao Sun; Hong-ming Zheng; Jin-long Zhang; Hong-hai Wang; Jia-Wei Fang; Ya-zheng Liu; Lin-ling Huang; Zhi-wen Song; Jin-bo Liu (Molecular Neurobiology, 2023)

Simultaneously optimizing radiative decay and up-conversion of triphenylamine-based thermally activated delayed fluorescence emitters to achieve efficient deep-red organic light-emitting diodes - Hao-Yu Yang; Heng-Yuan Zhang; Ming Zhang; Hao Zhuo; Hui Wang; Hui Lin; Si-Lu Tao; Cai-Jun Zheng; Xiao-Hong Zhang (Chemical Engineering Journal, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Ultralight, robust, and high Prussian blue-loading polyacrylonitrile aerogel: Preparation, characterization and efficient adsorption/removal of Cs+ - Xiao-Bo Yang; Wei Li; Ze-Zhong Lin; Jing-Qi Liu; Hong-Xin Jiang; Hao Jia; Wei-Liang Jin; Xin-Long Hou; Bing-Xuan Du; Li-Na Zhu; De-Ming Kong (Chemical Engineering Journal, 2023)

Design of the yielding support used highly deformable elements for a tunnel excavated in squeezing rock - Hong-ming Tian; Yun Tian; Wei-zhong Chen; Xian-jun Tan; Xiao-yun Shu; Xia-lin Liu (Journal of Mountain Science, 2023)

Effects of vegetation type differences induced by human disturbance on the nutrition strategy and gut microbiota of Siberian roe deer - Zi‐ao Yuan; Lin‐qiang Zhong; Hai‐rong Du; Jia‐nan Feng; Xin‐xin Liu; Hong‐yi Yuan; Jin‐hao Guo; Peng Liu; Ming‐hai Zhang (Molecular Ecology, 2023)
The Siberian roe deer ( Capreolus pygargus ) is a widely distributed ungulate in northeast China. Due to a series of human disturbance activities such as large‐scale forest cutting, deforestation and reclamation, road construction in the past, the appearance and internal structure of forest vegetation in the habitat of Siberian roe have changed significantly. At the same time, Siberian roe population had a series of ecological adaptation responses in the face of such habitat changes. Therefore, two typical vegetation types with differences were selected in the Muling Forest, China. We used nutritional ecology and microbial metagenomic analysis techniques to compare the nutritional selection strategy and the structure and functional characteristics of faecal microbiota of Siberian roe groups in two vegetation types. The results showed that the α diversity of dietary and gut microbes of deer in Natural Forest was higher than that in Plantation Forest. However, the gut microbes of the Plantation Forest group contained more unique enzymes in the functional pathways of carbon metabolism and biosynthesis of amino acids. This study suggests that habitat type is associated with plant community composition, and contributes to changes in the intake proportions of major macronutrients by altering the availability, quality, and composition of certain edible plants. Feeding behaviour may be an important regulatory factor of gut microbiota structure and function of deer. The metabolic function of gut microbiota to different nutrients may affect the microbial community structure. Therefore, our results suggest that the gut microbes of Siberian roe may have coevolved with their diets, and reflect the adaptability of deer populations to environmental changes (e.g., vegetation type). Our study provides new insights into how spatial heterogeneity affects nutrition and microecosystems by describing the interactions among the environment, diet, and symbiotic gut microbes in wild ungulates.

To what extent the traffic restriction policies can improve its air quality? An inspiration from COVID-19 - Si-qing Xu; Hong-di He; Ming-ke Yang; Cui-lin Wu; Xing-hang Zhu; Zhong-ren Peng; Yuya Sasaki; Kenji Doi; Shinji Shimojo (Stochastic Environmental Research and Risk Assessment, 2023)

Anisotropic creep behavior of soft-hard interbedded rock masses based on 3D printing and digital imaging correlation technology - Yun Tian; Fa-quan Wu; Hong-ming Tian; Zhe Li; Xiao-yun Shu; Lin-kai He; Man Huang; Wei-zhong Chen (Journal of Mountain Science, 2023)

ARSCP: An antimicrobial residue surveillance cloud platform for animal-derived foods - Jun-Jun Yu; Ya-Lin Hu; Cheng-Zheng Liu; Shuai-Bin Wu; Zi-Jian Zheng; Ze-Hua Cui; Li Chen; Tian Wei; Shi-Kai Sun; Jun Ning; Xiang Wen; Qiu-Yue Diao; et al. (Science of The Total Environment, 2023)

Stilbenes with potent cytotoxicity from the seedcases of Paeonia suffruticosa Andrews - Meng-Yue Yang; Zhao-Xiang Shao; Yue-Tong Wang; Yong-Lian Hou; Ding-Kang Zhu; Sha Chen; Ya-Hui Zhang; Fei Cao; Yong-Kui Jing; Bin Lin; Zhan-Lin Li; Da-Hong Li; et al. (Phytochemistry, 2023)

PGC-1α/NRF1-dependent cardiac mitochondrial biogenesis: A druggable pathway of calycosin against triptolide cardiotoxicity - Xiao-Ming Qi; Yuan-Biao Qiao; Yuan-Lin Zhang; Ai-Cheng Wang; Jin-Hong Ren; Hui-Zhi Wei; Qing-Shan Li (Food and Chemical Toxicology, 2023)

Andrographolide ameliorates hepatic steatosis by suppressing FATP2-mediated fatty acid uptake in mice with nonalcoholic fatty liver disease - Li-Sha Ran; Ya-Zeng Wu; Yi-Wen Gan; Hong-Lian Wang; Li-Juan Wu; Chun-Mei Zheng; Yao Ming; Ran Xiong; Yong-Lin Li; Shi-Hang Lei; Xue Wang; Xiao-Qing Lao; et al. (Journal of Natural Medicines, 2023)
Excessive intrahepatocellular lipid accumulation or steatosis is caused by abnormal lipid metabolism and a common character of nonalcoholic fatty liver disease (NAFLD), which may progress into cirrhosis and hepatocellular cancer. Andrographolide (Andro) is the primary active ingredient extracted from Andrographis paniculata , showing a protective role against dietary steatosis with the mechanism not fully understood. In this study, we showed that administration of Andro (50, 100, and 200 mg/kg/day for 8 weeks, respectively) attenuated obesity and metabolic syndrome in high-fat diet (HFD)-fed mice with improved glucose tolerance, insulin sensitivity, and reduced hyperinsulinemia, hyperglycemia, and hyperlipidemia. HFD-fed mice presented hepatic steatosis, which was significantly prevented by Andro. In vitro, Andro decreased the intracellular lipid droplets in oleic acid-treated LO2 cells. The selected RT-PCR array revealed a robust expression suppression of the fatty acid transport proteins (FATPs) by Andro treatment. Most importantly, we found that Andro consistently reduced the expression of FATP2 in both the oleic acid-treated LO2 cells and liver tissues of HFD-fed mice. Overexpression of FATP2 abolished the lipid-lowering effect of Andro in oleic acid-treated LO2 cells. Andro treatment also reduced the fatty acid uptake in oleic acid-treated LO2 cells, which was blunted by FATP2 overexpression. Collectively, our findings reveal a novel mechanism underlying the anti-steatosis effect of Andro by suppressing FATP2-mediated fatty acid uptake, suggesting the potential therapeutic application of Andro in the treatment of NAFLD. Graphical abstract

Transplantation of Nasal Olfactory Mucosa Mesenchymal Stem Cells Benefits Alzheimer’s Disease - Chun-Gu Hong; Meng-Lu Chen; Ran Duan; Xin Wang; Zhi-Lin Pang; Li-Te Ge; Ming Lu; Hui Xie; Zheng-Zhao Liu (Molecular Neurobiology, 2022)

Rapid Determination in the Quality Control of Chinese Patent Medicine - Shao Hua Lu; Ming Cai Zhang; Hong Lin Zhai; Ke Xin Bi; Bing Qiang Zhao (Journal of Pharmaceutical Innovation, 2022)

Breast cancer incidence in a national cohort of female workers exposed to special health hazards in Taiwan: a retrospective case-cohort study of ~ 300,000 occupational records spanning 20 years - Yun-Shiuan Chuang; Chun-Ying Lee; Pei-Chen Lin; Chih-Hong Pan; Hui-Min Hsieh; Chia-Fang Wu; Ming-Tsang Wu (International Archives of Occupational and Environmental Health, 2022)

Endothelial cells induce degradation of ECM through enhanced secretion of MMP14 carried on extracellular vesicles in venous malformation - Gao-Hong Chen; Jie-Gang Yang; Hou-Fu Xia; Lin-Zhou Zhang; Yin-Hsueh Chen; Kui-Ming Wang; Xu Duan; Lian-Zhi Wu; Yi-Fang Zhao; Gang Chen (Cell and Tissue Research, 2022)

Aquapteridospora jiangxiensis, a new aquatic hyphomycetous fungus from a freshwater habitat in China - Su-Qin Peng; Yu-Lin Liu; Jun-En Huang; Xiao-Hong Li; Xin-Yi Yan; Hai-Yan Song; Yang Gao; Zhi-Jun Zhai; Yuan-Qiu Liu; Dian-Ming Hu (Archives of Microbiology, 2022)

Estrogenic and anti-neutrophilic inflammatory phenanthrenes from Juncus effusus L. - Hao-Chun Hu; Yi-Hong Tsai; Yu-Che Chuang; Kuei-Hung Lai; Yu-Ming Hsu; Tsong-Long Hwang; Chih-Chan Lin; Ferenc Fülöp; Yang-Chang Wu; Szu-Yin Yu; Yu-Ting Kuo; Fang-Rong Chang (Natural Product Research, 2022)

Identification of the Largest SCA36 Pedigree in Asia: with Multimodel Neuroimaging Evaluation for the First Time - Yue Xie; Zhao Chen; Zhe Long; Rui-Ting Chen; Yi-Zheng Jiang; Ming-Jie Liu; Lin-Liu Peng; Hui-Rong Peng; Na Wan; Guangdong Zou; Chun-Rong Wang; Yu-Ting Shi; et al. (The Cerebellum, 2022)

Estrogen Deficiency Aggravates Fluoride-Induced Liver Damage and Lipid Metabolism Disorder in Rats - Ya-ming Yu; Bian-hua Zhou; Yi-lin Yang; Cheng-Xiang Guo; Jing Zhao; Hong-wei Wang (Biological Trace Element Research, 2022)

Morphological and Molecular Characterization of Paragonimus skrjabini Complex from Yunnan, China: A Brief Report - Qiu-Hong Shu; Shu-De Li; Ming Tian; Yong Meng; Shu-Mei-Qi He; Min Zhu; Miao-Miao Wang; Wen-Lin Wang (Acta Parasitologica, 2022)
Purpose To perform environmental sampling and molecular identification of Paragonimus in endemic regions, which may help in minimizing transmission among humans. Methods Mountain crabs from the genus Potamiscus were collected and the encysted metacercariae were extracted and subjected to morphological identification, followed by animal inoculation in Sprague–Dawley (SD) rats. After 112 days of infection, animals were killed and adult worms were extracted from lungs and muscles. The morphology of adult worms was characterized by microscopy and molecular identification was done by polymerase chain reaction, followed by sequencing of cox1 and ITS2 genes. Phylogenetic analysis was done by maximum parsimony method. Results A total of 447 crabs were captured from the streams of Tongchang Town, Jinping County, Yunnan Province, China. The infection rate was found to be 41% (186 out of 447 crabs). The metacercariae of Paragonimus skrjabini was identified by the characteristics round or spherical encysted form measuring 410 to 460 × 400 to 460 µm. After animal infection in SD rats, adults were presumptively confirmed to be P. skrjabini , which was also confirmed by gene amplification and sequence analysis of cox1 and ITS2 regions. Paragonimus skrjabini clustered with previously reported P. skrjabini from Yunnan and Vietnam. The confidence values of their branches were > 95%. Phylogenetic analysis of the ITS2 region revealed two distinct clusters with distinct geographical grouping. Phylogenetic analysis with the combined data sets reiterated the geographical grouping with P. skrjabini from Yunnan clustering with strains from Vietnam. Conclusion Metacercariae of P. skrjabini was discovered in freshwater crabs in Yunnan province, China, and the strains were phylogenetically related to P. skrjabini from Vietnam.

MoOpy2 is essential for fungal development, pathogenicity, and autophagy in Magnaporthe oryzae - Ying‐Ying Cai; Jing‐Yi Wang; Xi‐Yu Wu; Shuang Liang; Xue‐Ming Zhu; Lin Li; Jian‐Ping Lu; Xiao‐Hong Liu; Fu‐Cheng Lin (Environmental Microbiology, 2022)
Summary The development and pathogenicity of the fungus Magnaporthe oryzae , the causal agent of destructive rice blast disease, require it to perceive external environmental signals. Opy2, an overproduction‐induced pheromone‐resistant protein 2, is a crucial protein for sensing external signals in Saccharomyces cerevisiae . However, the biological functions of the homologue of Opy2 in M. oryzae are unclear. In this study, we identified that MoOPY2 is involved in fungal development, pathogenicity, and autophagy in M. oryzae . Deletion of MoOPY2 resulted in pleiotropic defects in hyphal growth, conidiation, germ tube extension, appressorium formation, appressorium turgor generation, and invasive growth, therefore leading to attenuated pathogenicity. Furthermore, MoOpy2 participates in the Osm1 MAPK pathway and the Mps1 MAPK pathway by interacting with the adaptor protein Mst50. The interaction sites of Mst50 and MoOpy2 colocalized with the autophagic marker protein MoAtg8 in the preautophagosomal structure sites (PAS). Notably, the Δ Moopy2 mutant caused cumulative MoAtg8 lipidation and rapid GFP‐MoAtg8 degradation in response to nitrogen starvation, showing that MoOpy2 is involved in the negative regulation of autophagy activity. Taken together, our study revealed that MoOpy2 of M. oryzae plays an essential role in the orchestration of fungal development, appressorium penetration, autophagy and pathogenesis.

Endosomal sorting complexes required for transport‐0 ( ESCRT ‐0) are essential for fungal development, pathogenicity, autophagy and ER ‐phagy in Magnaporthe oryzae - Li‐Xiao Sun; Hui Qian; Meng‐Yu Liu; Ming‐Hua Wu; Yun‐Yun Wei; Xue‐Ming Zhu; Jian‐Ping Lu; Fu‐Cheng Lin; Xiao‐Hong Liu (Environmental Microbiology, 2022)
Summary Magnaporthe oryzae is an important plant pathogen that causes rice blast. Hse1 and Vps27 are components of ESCRT‐0 involved in the multivesicular body (MVB) sorting pathway and biogenesis. To date, the biological functions of ESCRT‐0 in M. oryzae have not been determined. In this study, we identified and characterized Hse1 and Vps27 in M. oryzae . Disruption of MoHse1 and MoVps27 caused pleiotropic defects in growth, conidiation, sexual development and pathogenicity, thereby resulting in loss of virulence in rice and barley leaves. Disruption of MoHse1 and MoVps27 triggered increased lipidation of MoAtg8 and degradation of GFP‐MoAtg8, indicating that ESCRT‐0 is involved in the regulation of autophagy. ESCRT‐0 was determined to interact with coat protein complex II (COPII), a regulator functioning in homeostasis of the endoplasmic reticulum (ER homeostasis), and disruption of MoHse1 and MoVps27 also blocked activation of the unfolded protein response (UPR) and autophagy of the endoplasmic reticulum (ER‐phagy). Overall, our results indicate that ESCRT‐0 plays critical roles in regulating fungal development, virulence, autophagy and ER‐phagy in M. oryzae .

Prevalence, complete genome, and metabolic potentials of a phylogenetically novel cyanobacterial symbiont in the coral‐killing sponge, Terpios hoshinota - Yu‐Hsiang Chen; Hsing‐Ju Chen; Cheng‐Yu Yang; Jia‐Ho Shiu; Daphne Z. Hoh; Pei‐Wen Chiang; Wenhua Savanna Chow; Chaolun Allen Chen; Tin‐Han Shih; Szu‐Hsien Lin; Chi‐Ming Yang; James Davis Reimer; et al. (Environmental Microbiology, 2022)
Summary Terpios hoshinota is an aggressive, space‐competing sponge that kills various stony corals. Outbreaks of this species have led to intense damage to coral reefs in many locations. Here, the first large‐scale 16S rRNA gene survey across three oceans revealed that bacteria related to the taxa Prochloron , Endozoicomonas , SAR116, Ruegeria , and unclassified Proteobacteria were prevalent in T . hoshinota . A Prochloron ‐related bacterium was the most dominant and prevalent cyanobacterium in T . hoshinota . The complete genome of this uncultivated cyanobacterium and pigment analysis demonstrated that it has phycobiliproteins and lacks chlorophyll b , which is inconsistent with the definition of Prochloron . Furthermore, the cyanobacterium was phylogenetically distinct from Prochloron , strongly suggesting that it should be a sister taxon to Prochloron . Therefore, we proposed this symbiotic cyanobacterium as a novel species under the new genus Candidatus Paraprochloron terpiosi. Comparative genomic analyses revealed that ‘Paraprochloron’ and Prochloron exhibit distinct genomic features and DNA replication machinery. We also characterized the metabolic potentials of ‘Paraprochloron terpiosi’ in carbon and nitrogen cycling and propose a model for interactions between it and T. hoshinota . This study builds a foundation for the study of the T . hoshinota microbiome and paves the way for better understanding of ecosystems involving this coral‐killing sponge.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Identification and antimicrobial properties of a new alkaloid produced by marine-derived Verrucosispora sp. FIM06-0036 - Ming-Hong Chen; Yun-Yang Lian; Dong-Sheng Fang; Li Chen; Jia Jia; Wen-Long Zhang; Ru Lin; Yang Xie; Hong-Kai Bi; Hong Jiang (Natural Product Research, 2021)

Risk of two common glandular cell-type cancers (breast and colorectal cancers) in Chinese occupational chefs: a nationwide ecological study in Taiwan - Pei-Chen Lin; Chiung‑Yu Peng; Chih‑Hong Pan; Jui-Ying Lee; Tusty-Jiuan Hsieh; Yun-Shiuan Chuang; Robert J. Turesky; Chia-Fang Wu; Ming-Tsang Wu (International Archives of Occupational and Environmental Health, 2021)

Prenylated xanthones and biphenyls from Garcinia esculenta with antistaphylococcal activity - Dan Zheng; Hong Zhang; Jia-Ming Jiang; Yu-Yu Chen; Shi-Jie Wan; Zhi-Xiu Lin; Hong-Xi Xu (Natural Product Research, 2021)

Strong in vitro and in vivo cytotoxic effects of two platinum(II) complexes with cryptolepine derivatives - Li-Qin Qin; Zu-Zhuang Wei; Lin Yang; Qi-Pin Qin; Jia-Jing Zeng; Ming-Xiong Tan; Hong Liang (Medicinal Chemistry Research, 2021)

A luminescent Zn(II)-Containing Complex: Selective Sensing of Cr(VI) Anion and Application Values on Tuberculosis Care Through Increasing the Antibacterial Response of Macrophages - Jin-Chao Mao; Jin-Jing Hong; Ming-Zheng Lin; Feng Han; Dong Li (Journal of Fluorescence, 2021)

Environmental microorganism classification using optimized deep learning model - Chih-Ming Liang; Chun-Chi Lai; Szu-Hong Wang; Yu-Hao Lin (Environmental Science and Pollution Research, 2021)

Proton Pump Inhibitor Exposure and Acute Myocardial Infarction Risk: A Nested Cohort Study - Hsiang-Jung Tseng; Chih-Ming Cheng; Shih-Jen Tsai; Wei-Chen Lin; Ya-Mei Bai; Chia-Fen Tsai; Tung-Ping Su; Cheng-Ta Li; Tzeng-Ji Chen; Mu-Hong Chen (Cardiovascular Toxicology, 2021)

The response to flooding of two overwintering rice stem borers likely accounts for their changing impacts - Guang-Hua Luo; Zhi-Xin Luo; Zhi-Ling Zhang; Yang Sun; Ming-Hong Lu; Zhao-Lin Shu; Zi-Hua Tian; Ary A. Hoffmann; Ji-Chao Fang (Journal of Pest Science, 2021)

Phylogenetic analysis of infectious bronchitis virus circulating in southern China in 2016–2017 and evaluation of an attenuated strain as a vaccine candidate - Libin Chen; Bin Xiang; Yanfen Hong; Qian Li; Haoyun Du; Qiuyan Lin; Ming Liao; Tao Ren; Chenggang Xu (Archives of Virology, 2021)

Using sowing date management to promote micronutrient quality and alleviate cadmium accumulation in rice grains - Lin-lin Shi; Ming-xing Shen; Hong-jun Wu; Chang-ying Lu; Li-juan Mei; Xin-lian Zhu; Hai-hou Wang; Yun-Sheng Song (Cereal Research Communications, 2020)

One-pot synthesis of substituted pyrrole–imidazole derivatives with anticancer activity - Ming Zhang; Yong Ding; Hong-Xia Qin; Zhi-Gang Xu; Hai-Tao Lan; Dong-Lin Yang; Cheng Yi (Molecular Diversity, 2020)

Astrocytic GABAB Receptors in Mouse Hippocampus Control Responses to Behavioral Challenges through Astrocytic BDNF - Ji-Hong Liu; Ze-Lin Li; Yi-Si Liu; Huai-De Chu; Neng-Yuan Hu; Ding-Yu Wu; Lang Huang; Shu-Ji Li; Xiao-Wen Li; Jian-Ming Yang; Tian-Ming Gao (Neuroscience Bulletin, 2020)

Comparative transcriptomic analysis of fireflies (Coleoptera: Lampyridae) to explore the molecular adaptations to fresh water - Qi‐Lin Zhang; Hong‐Wei Li; Zhi‐Xiang Dong; Xiao‐Jie Yang; Lian‐Bing Lin; Jun‐Yuan Chen; Ming‐Long Yuan (Molecular Ecology, 2020)
Aquatic insects are well adapted to freshwater environments, but the molecular basis of these adaptations remains largely unknown. Most firefly species (Coleoptera: Lampyridae) are terrestrial, but the larvae of several species are aquatic. Here, larval and adult transcriptomes from Aquatica leii (freshwater) and Lychnuris praetexta (terrestrial) were generated to test whether the genes associated with metabolic efficiency and morphology have undergone adaptive evolution to fresh water. The aquatic fireflies had a significantly lower ratio of nonsynonymous to synonymous substitutions than the terrestrial insects, indicating a genomewide evolutionary constraint in the aquatic fireflies. We identified 341 fast‐evolving genes and 116 positively selected genes in the aquatic fireflies. Of these, 76 genes exhibiting both fast evolution and positive selection were primarily involved in ATP production, energy metabolism and the hypoxia response. We identified 7,271 differentially expressed genes (DEGs) in A . leii (adults versus larvae) and 8,309 DEGs in L . praetexta (adults versus larvae). DEGs specific to the aquatic firefly ( n = 1,445) were screened via interspecific comparisons ( A . leii versus L . praetexta ) and were significantly enriched for genes involved in metabolic efficiency (e.g., ATP production, hypoxia, and immune responses) and certain aspects of morphology (e.g., cuticle chitin, tracheal and compound eye morphology). These results indicate that sequence and expression‐level changes in genes associated with both metabolic efficiency and morphological attributes related to the freshwater lifestyle contributed to freshwater adaptation in fireflies. This study provides new insights into the molecular mechanisms of aquatic adaptation in insects.

Population Genetic Analysis for Stock Enhancement of Silver Sea Bream (Rhabdosargus sarba) in Taiwan - Te-Hua Hsu; Chang-Wen Huang; Hung-Tai Lee; Yi-Hsuan Kuo; Kwang-Ming Liu; Cheng-Hui Lin; Hong-Yi Gong (Fishes, 2020)
Stock enhancement is a method for replenishing depleted wild finfish populations by supplementing them with hatchery-raised fish. In Taiwan, silver sea bream (Rhabdosargus sarba) is a predominant commercial species involved in stock enhancement projects. Although management agencies conduct stock enhancement projects, there are a lot of private releases without records. Stock enhancement is performed by the private aquaculture sector without accurate genetic records, potentially leading to unintended consequences for wild populations. We analyzed the genetics of 459 wild and 701 hatchery-reared specimens from nine batches produced by various hatcheries. Wild and hatchery-reared samples could be considered two separate clades by using a set of stable and informative microsatellite markers including type I (from gene introns and 3′UTR) and type II markers (randomly picked up from genome). Type I microsatellite markers could more sensitively reflect the loss of genetic diversity more than type II markers in the domestication process. All specimens were considered native by using mtDNA COI and microsatellites. The genetic composition of the wild population is relatively simple, and the estimated low contribution rate of the hatchery stock (1.3–10.9%; 6–50/459) indicated a weak but significant genetic effect of stock enhancement. Therefore, establishing standards for the stock enhancement of silver sea bream for more effective supplementation of wild populations is imperative.

Short-term associations between ambient fine particulate matter pollution and hospital visits for chronic obstructive pulmonary disease in Yinzhou District, China - Cheng-yi Lin; Die Li; Jie-ming Lu; Zhe-bin Yu; Yao Zhu; Peng Shen; Meng-ling Tang; Ming-juan Jin; Hong-bo Lin; Li-ming Shui; Kun Chen; Jian-bing Wang (Environmental Science and Pollution Research, 2020)

Clinical strategies for differentiating IgG4-related cholecystitis from gallbladder carcinoma to avoid unnecessary surgical resection - Rui Zhang; Hao-Ming Lin; Zhao-Xi Cai; Su-Juan Du; Hong Zeng; Lei-Bo Xu; Jie Wang; Chao Liu (Science China Life Sciences, 2020)

Effects of Elevated Ozone Concentrations on Root Characteristics and Soil Properties of Elaeocarpus sylvestris and Michelia chapensis - Lan Pan; Wan-qi Lin; Ming Yu; Gan-wen Lie; Li Xue; Hong-yue Chen (Bulletin of Environmental Contamination and Toxicology, 2020)

Novel B-chromosome-specific transcriptionally active sequences are present throughout the maize B chromosome - Zi-Jie Hong; Jun-Xiang Xiao; Shu-Fen Peng; Yao-Pin Lin; Ya-Ming Cheng (Molecular Genetics and Genomics, 2020)

The m6A methyltransferase METTL3 cooperates with demethylase ALKBH5 to regulate osteogenic differentiation through NF-κB signaling - Jinjin Yu; Lujun Shen; Yanli Liu; Hong Ming; Xinxing Zhu; Maoping Chu; Juntang Lin (Molecular and Cellular Biochemistry, 2020)

A new indole-type alkaloid from the roots of Clematis florida var. plena - Kai-Hui Sun; Xin-Hua Ma; Xian-Ming Zeng; Zhong-Yue Lin; Yu-Mei Cai; Hai-Tao Zhang; Xiao-Yan Lin; Shi-Biao Feng; Tian-Hua Zhong; Yong-Hong Zhang (Natural Product Research, 2019)

Isolation, purification and identification of two new alkaloids metabolites from marine-derived Verrucosispora sp. FIM06025 - Ming-Hong Chen; Wen-Long Zhang; Li Chen; Ru Lin; Yang Xie; Dong-Sheng Fang; Yun-Yang Lian; Hong Jiang (Natural Product Research, 2019)

Estimation of monthly pan evaporation using support vector machine in Three Gorges Reservoir Area, China - Ji-Long Chen; Hong Yang; Ming-Quan Lv; Zuo-Lin Xiao; Sheng Jun Wu (Theoretical and Applied Climatology, 2019)

Endoscopic ultrasonography is useful in the diagnosis and treatment of rectal neuroendocrine neoplasms: a case series - Qing Gu; Yi-ming Lin; Li Cen; Min Xu; Hong-zhang Li; Xian-chu Lin; Chao Lu (Journal of Zhejiang University-SCIENCE B, 2019)

Recycled oceanic crust in the form of pyroxenite contributing to the Cenozoic continental basalts in central Asia: new perspectives from olivine chemistry and whole-rock B–Mo isotopes - Yunying Zhang; Chao Yuan; Min Sun; Ming Chen; Lubing Hong; Jie Li; Xiaoping Long; Pengfei Li; Zhengfan Lin (Contributions to Mineralogy and Petrology, 2019)

Effect of Feeding Strategies on Molecular Responses of Biotransformation Genes in Crassostrea gigas Exposed to Cadmium - Ming Sun; Guangbin Liu; Hong Lin; Tianwen Zhang; Wen Guo (Journal of Ocean University of China, 2019)

Rab18 Collaborates with Rab7 to Modulate Lysosomal and Autophagy Activities in the Nervous System: an Overlapping Mechanism for Warburg Micro Syndrome and Charcot-Marie-Tooth Neuropathy Type 2B - Fang-Shin Nian; Lei-Li Li; Chih-Ya Cheng; Pei-Chun Wu; You-Tai Lin; Cheng-Yung Tang; Bo-Shiun Ren; Chin-Yin Tai; Ming-Ji Fann; Lung-Sen Kao; Chen-Jee Hong; Jin-Wu Tsai (Molecular Neurobiology, 2019)

F‐box proteins MoFwd1, MoCdc4 and MoFbx15 regulate development and pathogenicity in the rice blast fungus Magnaporthe oryzae - Huan‐Bin Shi; Nan Chen; Xue‐Ming Zhu; Shuang Liang; Lin Li; Jiao‐Yu Wang; Jian‐Ping Lu; Fu‐Cheng Lin; Xiao‐Hong Liu (Environmental Microbiology, 2019)
Summary The Skp1‐Cul1‐F‐box‐protein (SCF) ubiquitin ligases are important parts of the ubiquitin system controlling many cellular biological processes in eukaryotes. However, the roles of SCF ubiquitin ligases remain unclear in phytopathogenic Magnaporthe oryzae . Here, we cloned 24 F‐box proteins and confirmed that 17 proteins could interact with MoSkp1, showing their potential to participate in SCF complexes. To determine their functions, null mutants of 21 F‐box‐containing genes were created. Among them, the F‐box proteins MoFwd1, MoCdc4 and MoFbx15 were found to be required for growth, development and full virulence. Fluorescent‐microscopy observations demonstrated that both MoFbx15 and MoCdc4 were localized to the nucleus, compared with MoFwd1, which was distributed in the cytosol. MoCdc4 and MoFwd1 bound to MoSkp1 via the F‐box domain, the deletion of which abrogated their function. Race tube and qRT‐PCR assays confirmed that MoFwd1 was involved in circadian rhythm by regulating transcription and protein stability of the core circadian clock regulator MoFRQ . Moreover, MoFWD1 also orchestrates conidial germination by influencing conidial amino acids pools and oxidative stress release. Overall, our results indicate that SCF ubiquitin ligases play indispensable roles in development and pathogenicity in M. oryzae .

Fuzzy Risk Assessment of Flash Floods Using a Cloud-Based Information Diffusion Approach - Ming Zhong; Jiao Wang; Liang Gao; Kairong Lin; Yang Hong (Water Resources Management, 2019)

A special issue to mark the 90th Anniversary of College of Life Sciences, Zhejiang University - Jin-rong Peng; Kun-liang Guan; De-yuan Hong; Xin-hua Lin; Huan-ming Yang; Yu-xian Zhu (Journal of Zhejiang University-SCIENCE B, 2019)

Expression of the intrarenal angiotensin receptor and the role of renin-angiotensin system inhibitors in IgA nephropathy - Zheng Zhang; Shi-min Jiang; Ye-ping Ma; Pei-lin Dai; Yi-ning Wang; Gu-ming Zou; Hong-mei Gao; Yue Yang; Wen-ge Li (Molecular and Cellular Biochemistry, 2019)

Correction to: Trichostatin A, a histone deacetylase inhibitor, induces synergistic cytotoxicity with chemotherapy via suppression of Raf/MEK/ERK pathway in urothelial carcinoma - Wei-Chou Lin; Fu-Shun Hsu; Kuan-Lin Kuo; Shing-Hwa Liu; Chia-Tung Shun; Chung-Sheng Shi; Hong-Chiang Chang; Yu-Chieh Tsai; Ming-Chieh Lin; June-Tai Wu; Yu Kuo; Po-Ming Chow; et al. (Journal of Molecular Medicine, 2019)

Pond-bottom decomposition of leaf litters canopied by free-floating vegetation - Ya-Lin Zhang; Hong-Bin Li; Li Xu; Xu Pan; Wen-Bing Li; Jian Liu; Yue-Ping Jiang; Yao-Bin Song; Ming Dong (Environmental Science and Pollution Research, 2019)

Ornithinimicrobium cavernae sp. nov., an actinobacterium isolated from a karst cave - Ling-Yu Zhang; Hong Ming; Xiao-Lin Meng; Bao-Zhu Fang; Jian-Yu Jiao; Nimaichand Salam; Xiao-Tong Zhang; Wen-Jun Li; Guo-Xing Nie (Antonie van Leeuwenhoek, 2019)

Gender differences and lung cancer risk in occupational chefs: analyzing more than 350,000 chefs in Taiwan, 1984–2011 - Pei-Chen Lin; Chiung-Yu Peng; Chih-Hong Pan; Pi-I Debby Lin; Ming-Tsang Wu (International Archives of Occupational and Environmental Health, 2019)

EGb761 improves the cognitive function of elderly db/db−/− diabetic mice by regulating the beclin-1 and NF-κB signaling pathways - Zhu-Fei Guan; Xiao-Ming Zhang; Ying-Hong Tao; Yu Zhang; Yan-Yan Huang; Gang Chen; Wei-Jun Tang; Gang Ji; Qi-Lin Guo; Ming Liu; Qian Zhang; Na-Na Wang; et al. (Metabolic Brain Disease, 2018)

Trichostatin A, a histone deacetylase inhibitor, induces synergistic cytotoxicity with chemotherapy via suppression of Raf/MEK/ERK pathway in urothelial carcinoma - Wei-Chou Lin; Fu-Shun Hsu; Kuan-Lin Kuo; Shing-Hwa Liu; Chia-Tung Shun; Chung-Sheng Shi; Hong-Chiang Chang; Yu-Chieh Tsai; Ming-Chieh Lin; June-Tai Wu; Yu Kuo; Po-Ming Chow; et al. (Journal of Molecular Medicine, 2018)

Tissue Section Image-Based Liver Scar Detection - Yung-Kuan Chan; Ming-Jen Chang; Yi-Wen Hung; Ching-Lin Wang; Chun-Fu Hong; Kwong-Chung Tung; Shyr Shen Yu (Journal of Medical and Biological Engineering, 2018)

Microsatellites development and cross-amplification for Aquilaria sinensis, an endangered agarwood-producing tree - Zheng-Feng Wang; Hong-Lin Cao; Chu-Xiong Cai; Yun Guo; Zhang-Ming Wang (Journal of Genetics, 2018)

Acute effect of fine and coarse particular matter on cardiovascular visits in Ningbo, China - Pei-wen Zheng; Peng Shen; Zhen-hua Ye; Zhen-yu Zhang; Peng-fei Chai; Die Li; Ming-juan Jin; Meng-Ling Tang; Huai-chu Lu; Hong-bo Lin; Jian-bing Wang; Kun Chen (Environmental Science and Pollution Research, 2018)

Multiscale analyses on a massive immigration process of Sogatella furcifera (Horváth) in south-central China: influences of synoptic-scale meteorological conditions and topography - Qiu-Lin Wu; John K. Westbrook; Gao Hu; Ming-Hong Lu; Wan-Cai Liu; Gregory A. Sword; Bao-Ping Zhai (International Journal of Biometeorology, 2018)

Extension of C. elegans lifespan using the ·NO-delivery dinitrosyl iron complexes - Hsiao-Wen Huang; Yen-Hung Lin; Min-Hsuan Lin; Ya-Rong Huang; Chih-Hung Chou; Hsiao-Chin Hong; Mei-Ren Wang; Yu-Ting Tseng; Po-Chun Liao; Min-Chuan Chung; Yu-Jie Ma; Shou-Cheng Wu; et al. (JBIC Journal of Biological Inorganic Chemistry, 2018)

BDNF/TrkB Pathway Mediates the Antidepressant-Like Role of H2S in CUMS-Exposed Rats by Inhibition of Hippocampal ER Stress - Le Wei; Li-Yuan Kan; Hai-Ying Zeng; Yi-Yun Tang; Hong-Lin Huang; Ming Xie; Wei Zou; Chun-Yan Wang; Ping Zhang; Xiao-Qing Tang (NeuroMolecular Medicine, 2018)

Social Isolation During Adolescence Induces Anxiety Behaviors and Enhances Firing Activity in BLA Pyramidal Neurons via mGluR5 Upregulation - Song Lin; Xin Li; Yi-Hua Chen; Feng Gao; Hao Chen; Neng-Yuan Hu; Lang Huang; Zheng-Yi Luo; Ji-Hong Liu; Qiang-Long You; Ya-Nan Yin; Ze-Lin Li; et al. (Molecular Neurobiology, 2018)

Phthalate esters distribution in coastal mariculture of Hong Kong, China - Zhang Cheng; Han-Han Li; Lin Yu; Zhan-Biao Yang; Xiao-Xun Xu; Hong-Sheng Wang; Ming-Hung Wong (Environmental Science and Pollution Research, 2018)

Association between short-term exposure to ambient air pollution and daily mortality: a time-series study in Eastern China - Die Li; Jian-bing Wang; Zhen-yu Zhang; Peng Shen; Pei-wen Zheng; Ming-juan Jin; Huai-chu Lu; Hong-bo Lin; Kun Chen (Environmental Science and Pollution Research, 2018)

Effect of nitrite exposure on oxygen-carrying capacity and gene expression of NF-κB/HIF-1α pathway in gill of bighead carp (Aristichthys nobilis) - Yan Lin; Ling-Hong Miao; Wu-Xiao Zhang; Wen-Jing Pan; Hua-Liang Liang; Xian-Ping Ge; Yan-Shun Xu; Bo Liu; Ming-Chun Ren; Qun-Lan Zhou; Si-Lei Xia (Aquaculture International, 2018)

Phylogenetic analysis of IRIS L. from China on chloroplast TRNL-F sequences - Yu-Lin Jiang; Zhuo Huang; Jin-Qiu Liao; Hui-Xing Song; Xiao-Mei Luo; Su-Ping Gao; Ting Lei; Ming-Yan Jiang; Yin Jia; Qi-Bing Chen; Xiao-Fang Yu; Yong-Hong Zhou (Biologia, 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

Effects of air pollution on hospital visits for pneumonia in children: a two-year analysis from China - Die Li; Jian-bing Wang; Zhen-yu Zhang; Peng Shen; Pei-wen Zheng; Ming-juan Jin; Huai-chu Lu; Hong-bo Lin; Kun Chen (Environmental Science and Pollution Research, 2018)

VPS9 domain‐containing proteins are essential for autophagy and endocytosis in Pyricularia oryzae - Xue‐Ming Zhu; Shuang Liang; Huan‐Bin Shi; Jian‐Ping Lu; Bo Dong; Qian‐Sheng Liao; Fu‐Cheng Lin; Xiao‐Hong Liu (Environmental Microbiology, 2018)
Summary Pyricularia oryzae is the causal pathogen of rice blast disease. Autophagy has been shown to play important roles in P . oryzae development and plant infection. The P. oryzae endosomal system is highly dynamic and has been shown to be associated with conidiogenesis and pathogenicity as well. To date, the crosstalk between autophagy and endocytosis has not been explored in P. oryzae . Here, we identified three P. oryzae VPS9 domain‐containing proteins, PoVps9, PoMuk1 and PoVrl1. We found that PoVps9 and PoMuk1 are localized to vesicles and are each co‐localized with PoVps21, a recognized marker of early endosomes. Deletion of PoVPS9 resulted in severe defects in endocytosis and autophagosome degradation and impaired the localization of PoVps21 to endosomes. Additionally, deletion of the PoMUK1 gene in the Δ Povps9 mutant background exhibited more severe defects in development, autophagy and endocytosis compared with the Δ Povps9 mutant. Pull‐down assay showed that PoVps9 interacts with PoVps21, PoRab11 and PoRab1, which have been verified to participate in endocytosis. Furthermore, yeast two‐hybrid and co‐immunoprecipitation assays confirmed that PoVps9 directly interacts with the GDP form of PoVps21. Thus, PoVps9 is a key protein involved in autophagy and in endocytosis.

Metaproteomics of marine viral concentrates reveals key viral populations and abundant periplasmic proteins in the oligotrophic deep chlorophyll maximum of the South China Sea - Zhang‐Xian Xie; Feng Chen; Shu‐Feng Zhang; Ming‐Hua Wang; Hao Zhang; Ling‐Fen Kong; Min‐Han Dai; Hua‐Sheng Hong; Lin Lin; Da‐Zhi Wang (Environmental Microbiology, 2018)
Summary Viral concentrates (VCs), containing bioinformative DNA and proteins, have been used to study viral diversity, viral metagenomics and virus–host interactions in natural ecosystems. Besides viruses, VCs also contain many noncellular biological components including diverse functional proteins. Here, we used a shotgun proteomic approach to characterize the proteins of VCs collected from the oligotrophic deep chlorophyll maximum (DCM) of the South China Sea. Proteins of viruses infecting picophytoplankton, that is, cyanobacteria and prasinophytes, and heterotrophic bacterioplankton, such as SAR11 and SAR116, dominated the viral proteome. Almost no proteins from RNA viruses or known gene transfer agents were detected, suggesting that they were not abundant at the sampling site. Remarkably, nonviral proteins made up about two thirds of VC proteins, including overwhelmingly abundant periplasmic transporters for nutrient acquisition and proteins for diverse cellular processes, that is, translation, energy metabolism and one carbon metabolism. Interestingly, three 56 kDa selenium‐binding proteins putatively involved in peroxide reduction from gammaproteobacteria were abundant in the VCs, suggesting active removal of peroxide compounds at DCM. Our study demonstrated that metaproteomics provides a valuable avenue to explore the diversity and structure of the viral community and also the pivotal biological functions affiliated with microbes in the natural environment.

Prevalence, mechanisms and genetic relatedness of the human pathogenic fungus Aspergillus fumigatus exhibiting resistance to medical azoles in the environment of Taiwan - Hsuan‐Chen Wang; Jui‐Chang Huang; Yong‐Hong Lin; Yu‐Hsin Chen; Ming‐I Hsieh; Pui‐Ching Choi; Hsiu‐Jung Lo; Wei‐Lun Liu; Ching‐Shan Hsu; Hsin‐I Shih; Chi‐Jung Wu; Yee‐Chun Chen (Environmental Microbiology, 2018)
Summary Emerging azole resistance in Aspergillus fumigatus poses a serious threat to human health. This nationwide surveillance study investigated the prevalence and molecular characteristics of azole‐resistant A. fumigatus environmental isolates in Taiwan, an island country with increasing use of azole fungicides. Of the 2760 air and soil samples screened from 2014 to 2016, 451 A. fumigatus isolates were recovered from 266 samples and 34 isolates from 29 samples displayed resistance to medical azoles (itraconazole, voriconazole or posaconazole). The resistance prevalence was 10.9% and 7.5% in A. fumigatus ‐positive samples and isolates respectively. Most (29, 85.3%) azole‐resistant isolates harboured TR 34 /L98H mutations, which were widely distributed, clustered genetically with clinical isolates, and had growth rates that were similar to those of the wild‐type isolates. Microsatellite genotyping revealed both the global spread of the TR 34 /L98H isolates and the occurrence of TR 34 /L98H/S297T/F495I isolates belonging to local microsatellite genotypes. AfuMDR3 and atrF , two efflux transporter genes, were constitutively upregulated in two individual resistant isolates without cyp51A mutations, highlighting their potential roles in azole resistance. These results emphasize the need for periodic environmental surveillance at the molecular level in regions in which azole fungicides are applied, and agricultural fungicide management strategies that generate less selective pressure should be investigated.

Bioaccumulation and biodegradation of sulfamethazine in Chlorella pyrenoidosa - Ming Sun; Hong Lin; Wen Guo; Fazhen Zhao; Jian Li (Journal of Ocean University of China, 2017)

Bioinformatic prediction and analysis of glucolipid metabolic regulation by miR-34a in Megalobrama amblycephala - Ling-Hong Miao; Wen-Jing Pan; Yan Lin; Xian-Ping Ge; Bo Liu; Ming-Chun Ren; Qun-Lan Zhou (Genes & Genomics, 2017)

α-Glucosidase inhibitors and phytotoxins from Streptomyces xanthophaeus - Jing Wei; Xiu-Yun Zhang; Shan Deng; Lin Cao; Quan-Hong Xue; Jin-Ming Gao (Natural Product Research, 2017)

Nocardia tengchongensis sp. nov., isolated from a soil sample - Shuai Li; Hong Ming; Yan-Yan Duan; Jian-Rong Huang; Zhuo-Li Zhao; Ling-Yu Zhang; Wei-Li Ji; Xiao-Lin Meng; Wen-Jun Li; Guo-Xing Nie (Antonie van Leeuwenhoek, 2017)

Down-Regulation of Neuregulin1/ErbB4 Signaling in the Hippocampus Is Critical for Learning and Memory - Jia Tian; Fei Geng; Feng Gao; Yi-Hua Chen; Ji-Hong Liu; Jian-Lin Wu; Yu-Jie Lan; Yuan-Ning Zeng; Xiao-Wen Li; Jian-Ming Yang; Tian-Ming Gao (Molecular Neurobiology, 2017)

Expression-based genotyping of the rice blast resistance genes in the elite maintainer line Yixiang1B - Li Wang; Xiao-Hong Hu; Gang Lin; De-Ming Zhao; Jun Shi; Zhi-Xue Zhao; Rui Zeng; Heng-Jing Li; De-Qiang Li; Jing Fan; Yan Li; Fu Huang; et al. (European Journal of Plant Pathology, 2017)

Air pollution and hospital visits for acute upper and lower respiratory infections among children in Ningbo, China: A time-series analysis - Pei-wen Zheng; Jian-bing Wang; Zhen-yu Zhang; Peng Shen; Peng-fei Chai; Die Li; Ming-juan Jin; Meng-Ling Tang; Huai-chu Lu; Hong-bo Lin; Kun Chen (Environmental Science and Pollution Research, 2017)

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

Quantification of mycotoxins in vegetable oil by UPLC-MS/MS after magnetic solid-phase extraction - Yan Zhao; Li-Hong Wan; Xiao-Lin Bai; Yi-Ming Liu; Feng-Ping Zhang; Yao-Min Liu; Xun Liao (Food Additives & Contaminants: Part A, 2017)

Oxygen microprofiles within the sediment-water interface studied by optode and its implication for aeration of polluted urban rivers - Bo Liu; Rui-ming Han; Wen-lin Wang; Hong Yao; Feng Zhou (Environmental Science and Pollution Research, 2017)

A novel thymidine phosphorylase mutation in a Chinese MNGIE patient - Hui-Fang Wang; Juan Wang; Yan-Ling Wang; Jian-Jian Fan; Gui-Lin Mo; Feng-Yin Gong; Zhi-Ming Chai; Jin Zhang; Hua-Xing Meng; Chang-Xin Li; Jun-Hong Guo; Chuan-Qiang Pu (Acta Neurologica Belgica, 2017)

NOX2 Mediated-Parvalbumin Interneuron Loss Might Contribute to Anxiety-Like and Enhanced Fear Learning Behavior in a Rat Model of Post-Traumatic Stress Disorder - Fang-fang Liu; Lin-dong Yang; Xiao-ru Sun; Hui Zhang; Wei Pan; Xing-ming Wang; Jian-jun Yang; Mu-huo Ji; Hong-mei Yuan (Molecular Neurobiology, 2016)

Ten polymorphic microsatellite markers characterized for Schizothorax pseudaksaiensis and applied for population genetic analysis - MING MING BAO; QIONG ZHOU; CONG XIN XIE; LIN GANG CAI; JIAN GONG NIU; HONG LI (Journal of Genetics, 2016)

Amycolatopsis xuchangensis sp. nov. and Amycolatopsis jiguanensis sp. nov., isolated from soil - Jian-Rong Huang; Hong Ming; Shuai Li; Zhuo-Li Zhao; Xiao-Lin Meng; Jian-Xin Zhang; Zhong Tang; Wen-Jun Li; Guo-Xing Nie (Antonie van Leeuwenhoek, 2016)

Synthesis and evaluation as potential antitumor agents of novel ursolic acid derivatives - Ming-Chuan Liu; Sheng-Jie Yang; Lin-Hong Jin; De-Yu Hu; Wei Xue; Song Yang (Medicinal Chemistry Research, 2016)

Goatpoxvirus ATPase activity is increased by dsDNA and decreased by zinc ion - Ming-Liang Lee; Wei-Li Hsu; Chi-Young Wang; Hui-Yu Chen; Fong-Yuan Lin; Ming-Huang Chang; Hong-You Chang; Min-Liang Wong; Kun-Wei Chan (Virus Genes, 2016)

BMP2 induces chondrogenic differentiation, osteogenic differentiation and endochondral ossification in stem cells - Nian Zhou; Qi Li; Xin Lin; Ning Hu; Jun-Yi Liao; Liang-Bo Lin; Chen Zhao; Zhen-Ming Hu; Xi Liang; Wei Xu; Hong Chen; Wei Huang (Cell and Tissue Research, 2016)

In Situ Field-Scale Remediation of Low Cd-Contaminated Paddy Soil Using Soil Amendments - Lin-feng Li; Shao-ying Ai; Yan-hong Wang; Ming-deng Tang; Yi-Chun Li (Water, Air, & Soil Pollution, 2016)

The relationship between plasma and urinary 8-hydroxy-2-deoxyguanosine biomarkers measured by liquid chromatography tandem mass spectrometry - Chung-Ching Wang; Wei-Liang Chen; Chien-Ming Lin; Ching-Huang Lai; Ching-Hui Loh; Hong-I Chen; Saou-Hsing Liou (Environmental Science and Pollution Research, 2016)

Paraventricular Nucleus Infusion of Epigallocatechin-3-O-Gallate Improves Renovascular Hypertension - Qiu-Yue Yi; Jie Qi; Xiao-Jing Yu; Hong-Bao Li; Yan Zhang; Qing Su; Tao Shi; Dong-Mei Zhang; Jing Guo; Zhi-Peng Feng; Mo-Lin Wang; Guo-Qing Zhu; et al. (Cardiovascular Toxicology, 2016)

New naphthopyrones from marine-derived fungus Aspergillus niger 2HL-M-8 and their in vitro antiproliferative activity - Da-Hong Li; Tong Han; Li-Ping Guan; Jiao Bai; Nan Zhao; Zhan-Lin Li; Xin Wu; Hui-Ming Hua (Natural Product Research, 2016)

Extracting Protein from Antarctic Krill ( Euphausia superba ) - Xiang-Ming Qi; E. Liao; Lu Wang; Hong Lin; Chang-Hu Xue (Journal of Aquatic Food Product Technology, 2016)

Pollen and seed flow under different predominant winds in wind-pollinated and wind-dispersed species Engelhardia roxburghiana - Zheng-Feng Wang; Ju-Yu Lian; Wan-Hui Ye; Hong-Lin Cao; Qian-Mei Zhang; Zhang-Ming Wang (Tree Genetics & Genomes, 2016)

Infralimbic Endothelin1 Is Critical for the Modulation of Anxiety-Like Behaviors - Lin-Lin Bi; Ming Chen; Lei Pei; Shu Shu; Hui-Juan Jin; Hong-Lin Yan; Na Wei; Shan Wang; Xin Yang; Huan-Huan Yan; Meng-meng Xu; Cheng-Ye Yao; et al. (Molecular Neurobiology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Social Isolation During Adolescence Strengthens Retention of Fear Memories and Facilitates Induction of Late-Phase Long-Term Potentiation - Ji-Hong Liu; Qiang-Long You; Mei-Dan Wei; Qian Wang; Zheng-Yi Luo; Song Lin; Lang Huang; Shu-JI Li; Xiao-Wen Li; Tian-Ming Gao (Molecular Neurobiology, 2015)

New Perspectives on Dietary-derived Treatments and Food Safety—Antinomy in a New Era - Si-Yuan Pan; Si-Hua Gao; Rui-Chao Lin; Shu-Feng Zhou; Hong-Guan Dong; Min-Ke Tang; Zhi-Ling Yu; Kam-Ming Ko (Critical Reviews in Food Science and Nutrition, 2015)

Using hybrid transcription factors to study gene function in rice - Tao Zhao; Jun Liu; Hong-Yu Li; Jian-Zhong Lin; Ming-Di Bian; Chun-Yu Zhang; Yong-Xing Zhang; Yu-Chong Peng; Bin Liu; ChenTao Lin (Science China Life Sciences, 2015)

Generation of insect-resistant and glyphosate-tolerant rice by introduction of a T-DNA containing two Bt insecticidal genes and an EPSPS gene - Qi-chao Zhao; Ming-hong Liu; Xian-wen Zhang; Chao-yang Lin; Qing Zhang; Zhi-cheng Shen (Journal of Zhejiang University-SCIENCE B, 2015)

Sinomonas halotolerans sp. nov., an actinobacterium isolated from a soil sample - Qian-Qian Guo; Hong Ming; Xiao-Lin Meng; Jian-Rong Huang; Yan-Yan Duan; Shan-Hui Li; Shuai Li; Jian-Xin Zhang; Wen-Jun Li; Guo-Xing Nie (Antonie van Leeuwenhoek, 2015)

Tropical SST forcing on the anomalous WNP subtropical high during July–August 2010 and the record-high SST in the tropical Atlantic - Chi-Cherng Hong; Ming-Ying Lee; Huang-Hsiung Hsu; Nai-Hsin Lin; Ben-Jei Tsuang (Climate Dynamics, 2015)

High immune activation and abnormal expression of cytokines contribute to death of SHIV89.6-infected Chinese rhesus macaques - Ren-Rong Tian; Ming-Xu Zhang; Lin-Tao Zhang; Xiao-Liang Zhang; Hong-Yi Zheng; Lin Zhu; Wei Pang; Gao-Hong Zhang; Yong-Tang Zheng (Archives of Virology, 2015)

ERK Is Involved in the Process of Acrosome Reaction In Vitro of the Chinese Mitten Crab, Eriocheir sinensis - Wen-Juan Sun; Ming Zhu; Yuan-Li Wang; Qing Li; Hong-Dan Yang; Ze-Lin Duan; Lin He; Qun Wang (Marine Biotechnology, 2015)

Arthroscopic Characteristics of Normal and Discoid Meniscus Injury, and Efficiency of Recovery in Each Type of Meniscus Injury - Xiao Ouyang; Bo Wei; Shi Dong Hong; Feng Xin; Lin Wang; Xiao Wei Yang; Li Ming Wang (Cell Biochemistry and Biophysics, 2015)

Study on the Mechanisms of Cartilage Tissue Damage Caused by Hydrogen Peroxide - Xiao Ouyang; Bo Wei; Shi Dong Hong; Jing Rong Wang; Feng Xin; Lin Wang; Xiao Wei Yang; Li Ming Wang (Cell Biochemistry and Biophysics, 2015)

Rapid detection of copper chlorophyll in vegetable oils based on surface-enhanced Raman spectroscopy - Wei-Nan Lian; Jessie Shiue; Huai-Hsien Wang; Wei-Chen Hong; Po-Han Shih; Chao-Kai Hsu; Ching-Yi Huang; Cheng-Rong Hsing; Ching-Ming Wei; Juen-Kai Wang; Yuh-Lin Wang (Food Additives & Contaminants: Part A, 2015)

The Marginal Division of the Striatum and Hippocampus Has Different Role and Mechanism in Learning and Memory - Si-Yun Shu; Gang Jiang; Qi-Yi Zeng; Bin Wang; Hong Li; Lin Ma; Harry Steinbusch; Cai Song; Wood-Yee Chan; Xu-Hong Chen; Yon-Ming Wu; Rong Bao; et al. (Molecular Neurobiology, 2015)

Human health risk assessment of soil dioxin/furans contamination and dioxin-like activity determined by ethoxyresorufin-O-deethylase bioassay - Yu Bon Man; Ka Lai Chow; Hong Sheng Wang; Xiao Lin Sun; Sheng Chun Wu; Zong Wei Cai; Yuan Kang; Hui Li; Jin Shu Zheng; John P. Giesy; Ming Hung Wong (Environmental Science and Pollution Research, 2015)

Phylogenetic and recombination analysis of rice black-streaked dwarf virus segment 9 in China - Yu Zhou; Jian-Feng Weng; Yan-Ping Chen; Chang-Lin Liu; Xiao-Hua Han; Zhuan-Fang Hao; Ming-Shun Li; Hong-Jun Yong; De-Gui Zhang; Shi-Huang Zhang; Xin-Hai Li (Archives of Virology, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Anxiolytic effects of ketamine in animal models of posttraumatic stress disorder - Li-Ming Zhang; Wen-Wen Zhou; Ya-Jun Ji; Ying Li; Nan Zhao; Hong-Xia Chen; Rui Xue; Xin-Guo Mei; You-Zhi Zhang; Heng-Lin Wang; Yun-Feng Li (Psychopharmacology, 2015)

Stress signaling in response to polycyclic aromatic hydrocarbon exposure in Arabidopsis thaliana involves a nucleoside diphosphate kinase, NDPK-3 - Hong Liu; David Weisman; Ling Tang; Long Tan; Wen-ke Zhang; Zong-hua Wang; Yan-he Huang; Wen-xiong Lin; Xuan-ming Liu; Adán Colón-Carmona (Planta, 2015)

Establishment of an Agrobacterium-mediated genetic transformation procedure for the experimental model orchid Erycina pusilla - Shu-Hong Lee; Chia-Wen Li; Chia-Hui Liau; Pao-Yi Chang; Li-Jen Liao; Choun-Sea Lin; Ming-Tsair Chan (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Retraction Note to: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Double homeobox gene, Duxbl, promotes myoblast proliferation and abolishes myoblast differentiation by blocking MyoD transactivation - Shey-Lin Wu; Guo-Zili Li; Chin-Yi Chou; Ming-Shiun Tsai; Yi-Pei Chen; Chung-Jung Li; Gan-Guang Liou; Wen-Wei Chang; Shen-Liang Chen; Sue-Hong Wang (Cell and Tissue Research, 2014)

Galectin-1 induces vascular permeability through the neuropilin-1/vascular endothelial growth factor receptor-1 complex - Ming-Heng Wu; Nien-Wen Ying; Tse-Ming Hong; Wei-Fan Chiang; Yueh-Te Lin; Yuh-Ling Chen (Angiogenesis, 2014)

CbCBF from Capsella bursa-pastoris enhances cold tolerance and restrains growth in Nicotiana tabacum by antagonizing with gibberellin and affecting cell cycle signaling - Mingqi Zhou; Ming Xu; Lihua Wu; Chen Shen; Hong Ma; Juan Lin (Plant Molecular Biology, 2014)

Fast and Highly Efficient Removal of Chromate from Aqueous Solution Using Nanoscale Zero-Valent Iron/Activated Carbon (NZVI/AC) - Chun-Hua Xu; Liu-jia Zhu; Xiao-Hong Wang; Sheng Lin; Ya-ming Chen (Water, Air, & Soil Pollution, 2014)

Three new diterpenoids from the resin of Liquidambar formosana - Hong-Jie Shang; Dan-Yi Li; Wen-Jing Wang; Zhan-Lin Li; Hui-Ming Hua (Natural Product Research, 2014)

Artificial antigen synthesis and the development of polyclonal antibody-based immunoassay for citreoviridin determination - Zhen Hong Zhuang; Shan Jin Que; Yue Ming Gao; Jun Yuan; Zhou Ye; Min Du; Guang Mei Lin; Li Cai Liu; Shi Hua Wang (World Journal of Microbiology and Biotechnology, 2014)

A new indole alkaloidal glucoside from the aerial parts of Clematis terniflora DC. - Wen-Ting Li; Bing-Xian Yang; Wei Zhu; Ming-Hua Gong; Xiang-Dong Xu; Xiang-Hong Lu; Lian-Li Sun; Jing-Kui Tian; Lin Zhang (Natural Product Research, 2013)

The roles of two transcription factors, ABI4 and CBFA, in ABA and plastid signalling and stress responses - Zhong-Wei Zhang; Ling-Yang Feng; Jian Cheng; He Tang; Fei Xu; Feng Zhu; Zhong-Yi Zhao; Ming Yuan; Yang-Er Chen; Jian-Hui Wang; Shu Yuan; Hong-Hui Lin (Plant Molecular Biology, 2013)

Genetic and epigenetic differentiation between natural Betula ermanii (Betulaceae) populations inhabiting contrasting habitats - Wei-Qing Wu; Ma Re Yi; Xin-Feng Wang; Li-Li Ma; Lily Jiang; Xi-Wen Li; Hong-Xing Xiao; Ming-Zhou Sun; Lin-Feng Li; Bao Liu (Tree Genetics & Genomes, 2013)

Cell Hypertrophy and MEK/ERK Phosphorylation are Regulated by Glyceraldehyde-Derived AGEs in Cardiomyocyte H9c2 Cells - Shun-Yao Ko; I-Hsuan Lin; Tzong-Ming Shieh; Hsin-An Ko; Hong-I Chen; Tzong-Cherng Chi; Shu-Shing Chang; Yi-Chiang Hsu (Cell Biochemistry and Biophysics, 2013)

RETRACTED ARTICLE: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

The active alkaloids of Gelsemium elegans Benth. are potent anxiolytics - Ming Liu; Hui-Hui Huang; Jian Yang; Yan-Ping Su; Hong-Wei Lin; Li-Qing Lin; Wei-Jian Liao; Chang-Xi Yu (Psychopharmacology, 2013)

Manganese-Induced Effects on Testicular Trace Element Levels and Crucial Hormonal Parameters of Hyline Cocks - Xiao-fei Liu; Li-ming Zhang; Ziwei Zhang; Ning Liu; Shi-wen Xu; Hong-jin Lin (Biological Trace Element Research, 2013)

Molecular epidemiology of PRRSV from China’s Guangxi Province between 2007 and 2009 - Hong-Yun Zhang; Jing-Jing Liang; Xian-Ming Meng; Hui Li; Jian Yang; Li-Juan Su; Hong-Pu Zhang; Lin-Juan Xie; Xiao-Xia He; Yan-Sheng Li; Shan Yin; Xiao-Quan Li; et al. (Virus Genes, 2013)

Atypical work schedules are associated with poor sleep quality and mental health in Taiwan female nurses - Pei-Chen Lin; Chung-Hey Chen; Shung-Mei Pan; Chih-Hong Pan; Chiou-Jong Chen; Yao-Mei Chen; Hsin-Chia Hung; Ming-Tsang Wu (International Archives of Occupational and Environmental Health, 2012)

Multi-environment mapping and meta-analysis of 100-seed weight in soybean - Ya-nan Sun; Jun-bo Pan; Xiang-lin Shi; Xiang-yu Du; Qiong Wu; Zhao-ming Qi; Hong-wei Jiang; Da-wei Xin; Chun-yan Liu; Guo-hua Hu; Qing-shan Chen (Molecular Biology Reports, 2012)

Effects of fertilization and drought stress on tannin biosynthesis of Casuarina equisetifolia seedlings branchlets - Li Hua Zhang; Hong Bo Shao; Gong Fu Ye; Yi Ming Lin (Acta Physiologiae Plantarum, 2012)

Production of monoclonal antibody and application in indirect competitive ELISA for detecting okadaic acid and dinophytoxin-1 in seafood - Shi-Ying Lu; Yu Zhou; Yan-Song Li; Chao Lin; Xian-Mei Meng; Dong-Ming Yan; Zhao-Hui Li; Shi-Yu Yu; Zeng-Shan Liu; Hong-Lin Ren (Environmental Science and Pollution Research, 2012)

The mitochondrial genome of the quiet-calling katydids, Xizicus fascipes (Orthoptera: Tettigoniidae: Meconematinae) - MING RU YANG; ZHI JUN ZHOU; YAN LIN CHANG; LE HONG ZHAO (Journal of Genetics, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

VEGF is essential for the growth and migration of human hepatocellular carcinoma cells - Lei Zhang; Jia-Ning Wang; Jun-Ming Tang; Xia Kong; Jian-Ye Yang; Fei Zheng; Ling-Yun Guo; Yong-Zhang Huang; Li Zhang; Lin Tian; Shu-Fen Cao; Chang-Hai Tuo; et al. (Molecular Biology Reports, 2012)

Effects of isoflurane exposure during pregnancy on postnatal memory and learning in offspring rats - Fei-juan Kong; Yu-wen Tang; Ai-fei Lou; Hong Chen; Lin-hao Xu; Xiao-ming Zhang; Hui-shun Lu (Molecular Biology Reports, 2012)

Sucrose treatment alters floral induction and development in vitro in gloxinia - Ming-Zhe Zhang; Li-Ling Wang; Dan Ye; Xi Chen; Zhi-Yi Wu; Xiao-Jia Lin; Wu-Jian Chen; Hong-Wu Bian; Ning Han; Mu-Yuan Zhu (In Vitro Cellular & Developmental Biology - Plant, 2012)

Preferential involvement of mitochondria in Toll-like receptor 3 agonist-induced neuroblastoma cell apoptosis, but not in inhibition of cell growth - Jiin-Haur Chuang; Tsu-Kung Lin; Ming-Hong Tai; Chia-Wei Liou; Sheng-Teng Huang; Chia-Ling Wu; Hung-Yi Lin; Pei-Wen Wang (Apoptosis, 2012)

Neuroprotection by marine-derived compound, 11-dehydrosinulariolide, in an in vitro Parkinson’s model: a promising candidate for the treatment of Parkinson’s disease - Wu-Fu Chen; Chiranjib Chakraborty; Chun-Sung Sung; Chien-Wei Feng; Yen-Hsuan Jean; Yen-You Lin; Han-Chun Hung; Tzu-Yi Huang; Shi-Ying Huang; Thung-Ming Su; Ping-Jyun Sung; Jyh-Horng Sheu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2012)

PC-based artificial neural network inversion for airborne time-domain electromagnetic data - Kai-Guang Zhu; Ming-Yao Ma; Hong-Wei Che; Er-Wei Yang; Yan-Ju Ji; Sheng-Bao Yu; Jun Lin (Applied Geophysics, 2012)

A Promising CdSe@CdS-Quantum Dots-Cysteine for the Determination of Trace IgE by Solid Substrate Room Temperature Phosphorescence Immunoassay - Jia-Ming Liu; Li-ping Lin; Zhen-Bo Liu; Min-Lan Yang; Xin-xing Wang; Li-hong Zhang; Ma-lin Cui; Li Jiao (Journal of Fluorescence, 2012)

QTL detection of seven quality traits in wheat using two related recombinant inbred line populations - Jun Li; Fa Cui; An-ming Ding; Chun-hua Zhao; Xiu-qin Wang; Lin Wang; Yin-guang Bao; Xiao-lei Qi; Xing-feng Li; Ju-rong Gao; De-shun Feng; Hong-gang Wang (Euphytica, 2012)

The backend design of an environmental monitoring system upon real-time prediction of groundwater level fluctuation under the hillslope - Hsueh-Chun Lin; Yao-Ming Hong; Yao-Chiang Kan (Environmental Monitoring and Assessment, 2012)

Isolation and identification of an acetoin high production bacterium that can reverse transform 2,3-butanediol to acetoin at the decline phase of fermentation - Xian Zhang; Tao-wei Yang; Qing Lin; Mei-juan Xu; Hai-feng Xia; Zheng-hong Xu; Hua-zhong Li; Zhi-ming Rao (World Journal of Microbiology and Biotechnology, 2011)

Streptomyces shenzhenensis sp. nov., a novel actinomycete isolated from mangrove sediment - Huo Hu; Hai-Peng Lin; Qingyi Xie; Lei Li; Xin-Qiang Xie; Ming Sun; Kui Hong (Antonie van Leeuwenhoek, 2011)

No Association of Angiotensin I Converting Enzyme I/D Polymorphism with Domain-Specific Cognitive Function in Aged Men without Dementia - Mu-En Liu; Shih-Jen Tsai; Ti Lu; Cheng-Jee Hong; Ming-Chao Chen; Shoa-Lin Lin; Heng-Liang Yeh; Yan-Chiou Ku (NeuroMolecular Medicine, 2011)

Regulation of expression of trehalose-6-phosphate synthase during cold shock in Arthrobacter strain A3 - Xi-Ming Chen; Ying Jiang; Yuan-Ting Li; Hai-Hong Zhang; Jie Li; Xing Chen; Qi Zhao; Jing Zhao; Jing Si; Zhi-Wei Lin; Hua Zhang; Paul Dyson; et al. (Extremophiles, 2011)

A comparative study on arsenic and humic substances in alluvial aquifers of Bengal delta plain (NW Bangladesh), Chianan plain (SW Taiwan) and Lanyang plain (NE Taiwan): implication of arsenic mobilization mechanisms - A. H. M. Selim Reza; Jiin-Shuh Jean; Huai-Jen Yang; Ming-Kuo Lee; Hua-Fen Hsu; Chia-Chuan Liu; Yao-Chang Lee; Jochen Bundschuh; Kao-Hong Lin; Chi-Yu Lee (Environmental Geochemistry and Health, 2011)

Rhizobium sphaerophysae sp. nov., a novel species isolated from root nodules of Sphaerophysa salsula in China - Lin Xu; Jian Feng Shi; Peng Zhao; Wei Min Chen; Wei Qin; Ming Tang; Ge Hong Wei (Antonie van Leeuwenhoek, 2011)

Bacteria associated with an encrusting sponge ( Terpios hoshinota ) and the corals partially covered by the sponge - Sen‐Lin Tang; Mei‐Jhu Hong; Ming‐Hui Liao; Wann‐Neng Jane; Pei‐Wen Chiang; Chung‐Bin Chen; Chaolun A. Chen (Environmental Microbiology, 2011)
Summary Terpios hoshinota , a dark encrusting sponge, is known to be a competitor for space in coral reef environments, and facilitates the death of corals. Although numerous cyanobacteria have been detected in the sponge, little is known of the sponge‐associated bacterial community. This study examined the sponge‐associated bacterial community and the difference between the bacterial communities in the sponge and the coral partially covered by the sponge by analysis of 16S rRNA gene sequences of samples isolated from the sponge covering the corals Favia complanata, Isopora palifera, Millepora sp. , Montipora efflorescens and Porites lutea . The sponge‐associated bacterial community was mainly (61–98%) composed of cyanobacteria, with approximately 15% of these alphaproteobacteria and gammaproteobacteria, although the proportions varied in different sponge samples. The dominant cyanobacteria group was an isolated group closely related to Prochloron sp. The comparison of the bacterial communities isolated from sponge‐free and the sponge‐covered P. lutea showed that covering by the sponge caused changes in the coral‐associated bacterial communities, with the presence of bacteria similar to those detected in black‐band disease, suggesting the sponge might benefit from the presence of bacteria associated with unhealthy coral, particularly in the parts of the coral closest to the margin of the sponge.

Enrichment of cardiac differentiation of mouse embryonic stem cells by optimizing the hanging drop method - Ming Chen; Yong-Qing Lin; Shuang-Lun Xie; Hong-Fu Wu; Jing-Feng Wang (Biotechnology Letters, 2011)

Comparative expression analysis of dehydrins between two barley varieties, wild barley and Tibetan hulless barley associated with different stress resistance - Jun-Bo Du; Shu Yuan; Yang-Er Chen; Xin Sun; Zhong-Wei Zhang; Fei Xu; Ming Yuan; Jing Shang; Hong-Hui Lin (Acta Physiologiae Plantarum, 2011)

Geochemical and zircon U–Pb study of the Huangmeijian A-type granite: implications for geological evolution of the Lower Yangtze River belt - He Li; Hong Zhang; Ming-Xing Ling; Fang-Yue Wang; Xing Ding; Ji-Bin Zhou; Xiao-Yong Yang; Xiang-Lin Tu; Weidong Sun (International Geology Review, 2011)

The genetic association of adakites and Cu–Au ore deposits - Weidong Sun; Hong Zhang; Ming-Xing Ling; Xing Ding; Sun-Lin Chung; Jibin Zhou; Xiao-Yong Yang; Weiming Fan (International Geology Review, 2011)

Improved Osmotic Tolerance and Ethanol Production of Ethanologenic Escherichia coli by IrrE, a Global Regulator of Radiation-Resistance of Deinococcus radiodurans - Ruiqiang Ma; Ying Zhang; Haozhou Hong; Wei Lu; Min Lin; Ming Chen; Wei Zhang (Current Microbiology, 2011)

Eucommia ulmoides Oliv. antagonizes H2O2-induced rat osteoblastic MC3T3-E1 apoptosis by inhibiting expressions of caspases 3, 6, 7, and 9 - Jun Lin; Yi-jing Fan; Christian Mehl; Jia-jun Zhu; Hong Chen; Ling-yan Jin; Jing-hong Xu; Hui-ming Wang (Journal of Zhejiang University-SCIENCE B, 2011)

Determination of Trace Deoxyribonucleic Acid by Using Fluorescein Isothiocyanate-Phenosafranine as a Double-Luminescent Phosphorescence Probe - Jia-Ming Liu; Xiao-Mei Huang; Zhen-Bo Liu; Fei-Ming Li; Li-Ping Lin; Xin-Xing Wang; Chang-Qing Lin; Ya-Hong Huang; Zhi-Ming Li; Shao-Qin Lin (Journal of Fluorescence, 2011)

Human herpesvirus 8 viral FLICE-inhibitory protein retards cell proliferation via downregulation of Id2 and Id3 expression - Yi-Fen Wang; Lin-Yu Wang; Yi-Ling Li; Huey-Wen Shyu; Yee-Hsuan Chiou; Miao-Chen Chou; Kuan-Hua Lin; Ming-Hong Tai; Chang-Yu Chen (Molecular and Cellular Biochemistry, 2010)

Regulation of the seasonal population patterns of Helicoverpa armigera moths by Bt cotton planting - Yu-lin Gao; Hong-qiang Feng; Kong-ming Wu (Transgenic Research, 2010)

Over-expression of the AtGA2ox8 gene decreases the biomass accumulation and lignification in rapeseed (Brassica napus L.) - Xiao-ying Zhao; Deng-feng Zhu; Bo Zhou; Wu-sheng Peng; Jian-zhong Lin; Xing-qun Huang; Re-qing He; Yu-hong Zhuo; Dan Peng; Dong-ying Tang; Ming-fang Li; Xuan-ming Liu (Journal of Zhejiang University-SCIENCE B, 2010)

A New Phosphorimetry for the Determination of Trace Alkaline Phosphatase Using Multi-wall Carbon Nanotubes and Its Diagnosis of Human Diseases - Jia-Ming Liu; Ying Rao; Li Chen; Xin-Xing Wang; Li-Ping Lin; Chang-Qing Lin; Li-Hong Zhang; Ying Ou-Yang (Journal of Fluorescence, 2010)

Sensitive Phosphorimetric Determination of Bumetanide in Human Urine with Its Inhibition Effect on the Formation of [Fe-morin] 3+ Complex - Li-Qing Zeng; Jia-Ming Liu; Fei-Ming Li; Xiao-Mei Huang; Li-Ping Lin; Xin-Xing Wang; Li-Hong Zhang; Chang-Qing Lin (Journal of Fluorescence, 2010)

Effects of land cover changes induced by large physical disturbances on hydrological responses in Central Taiwan - Nien Ming Hong; Hone-Jay Chu; Yu-Pin Lin; Dung-Po Deng (Environmental Monitoring and Assessment, 2010)

Livin abrogates apoptosis of SPC-A1 cell by regulating JNKI signaling pathway - Yu-Sheng Chen; Hong-Ru Li; Ming Lin; Gang Chen; Bao-Song Xie; Neng-Luan Xu; Li-Fang Lin (Molecular Biology Reports, 2010)

Geniposide inhibits interleukin-6 and interleukin-8 production in lipopolysaccharide-induced human umbilical vein endothelial cells by blocking p38 and ERK1/2 signaling pathways - Hong-Tao Liu; Jun-Lin He; Wen-Ming Li; Zhu Yang; Ying-Xiong Wang; Juan Yin; Yu-Guang Du; Chao Yu (Inflammation Research, 2010)

Cloning and Characterization of ApRab4, a Recycling Rab Protein of Aiptasia pulchella, and Its Implication in the Symbiosome Biogenesis - Ming-Cheng Hong; Yung-Sen Huang; Pa-Ching Song; Wen-Wen Lin; Lee-Shing Fang; Ming-Chyuan Chen (Marine Biotechnology, 2009)

Takayasu’s arteritis associated with Crohn’s disease - You-shi Liu; You-hong Fang; Ling-xiang Ruan; You-ming Li; Lin Li; Ling-ling Jiang (Journal of Zhejiang University-SCIENCE B, 2009)

Salicylic acid activates artemisinin biosynthesis in Artemisia annua L. - Gao-Bin Pu; Dong-Ming Ma; Jian-Lin Chen; Lan-Qing Ma; Hong Wang; Guo-Feng Li; He-Chun Ye; Ben-Ye Liu (Plant Cell Reports, 2009)

Analyzing the shear strength parameters of the Chiu-fen-erh-shan landslide: integrating strong-motion and GPS data to determine the best-fit accelerogram - Jian-Hong Wu; Hung-Ming Lin (GPS Solutions, 2009)

Overexpression of the cucumber LEAFY homolog CFL and hormone treatments alter flower development in gloxinia (Sinningia speciosa) - Ming-Zhe Zhang; Dan Ye; Li-Lin Wang; Ji-Liang Pang; Yu-Hong Zhang; Ke Zheng; Hong-Wu Bian; Ning Han; Jian-Wei Pan; Jun-Hui Wang; Mu-Yuan Zhu (Plant Molecular Biology, 2008)

Induction of apoptosis in rabbit oral mucosa by 1.23% acidulated phosphate fluoride gel - Chia-Ling Tsai; Jui-Wei Lin; Hsi-Kung Kuo; Ming-Hong Tai; Yi-Chen Wu; Chih-Rong Shyr; Pei-Chang Wu (Archives of Toxicology, 2008)

Increase of multi-metal tolerance of three leguminous plants by arbuscular mycorrhizal fungi colonization - Ai-Jun Lin; Xu-Hong Zhang; Ming-Hung Wong; Zhi-Hong Ye; Lai-Qing Lou; You-Shan Wang; Yong-Guan Zhu (Environmental Geochemistry and Health, 2007)

The Endo-β-Mannanase gene families in Arabidopsis, rice, and poplar - Joshua S. Yuan; Xiaohan Yang; Jingru Lai; Hong Lin; Zong-Ming Cheng; Hiroyuki Nonogaki; Feng Chen (Functional & Integrative Genomics, 2006)

Characterization of CMS and maintainer lines in indica rice (Oryza sativa L.) based on RAPD marker analysis - Masahiko Ichii; De Lin Hong; Yoshinori Ohara; Chang Ming Zhao; Shin Taketa (Euphytica, 2003)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Multiple genotypes of mitochondrial DNA within a horse population from a small region in Yunnan province of China - Wen Wang; Ai-hua Liu; Shi-ying Lin; Hong Lan; Bing Su; De-wen Xie; Li-ming Shi (Biochemical Genetics, 1994)

Multiple genotypes of mitochondrial DNA within a horse population from a small region in Yunnan province of China - Wen Wang; Ai-hua Liu; Shi-ying Lin; Hong Lan; Bing Su; De-wen Xie; Li-ming Shi (Biochemical Genetics, 1994)